Acetal compound of ethylene vinyl alcohol copolymer, and composition containing the acetal compound
Patent Information
- Application Number
- JP2023114875
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-12
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2042-03-28
AI Technical Summary
Existing interlayer films for laminated glass do not adequately maintain transparency and exhibit sufficient heat resistance and creep resistance in high-temperature environments, with sheets containing vinyl acetal copolymers showing inconsistencies in self-supporting properties.
An acetalized product of ethylene vinyl alcohol copolymer is developed, with specific compositional and structural parameters including a symmetry coefficient of 0.75 to 1.00, a Tm/Tg ratio of 1.27 to 1.35, and a meso/racemo ratio of less than 5, ensuring excellent self-supporting properties and creep resistance in high-temperature environments while maintaining transparency.
The acetalized ethylene vinyl alcohol copolymer product forms a resin sheet that maintains transparency and provides enhanced self-supporting and creep resistance in high-temperature conditions, ensuring the integrity of laminated glass even under extreme heat.
Smart Images

Figure 00000058_0000 
Figure 00000058_0001
Abstract
Description
[Technical Field]
[0001] The present invention relates to an acetalized ethylene vinyl alcohol copolymer, a method for producing the same, a composition containing the acetalized ethylene vinyl alcohol copolymer, a resin sheet containing the composition, an interlayer for laminated glass made from the resin sheet, and laminated glass having the interlayer. [Background technology]
[0002] Laminated glass is safer because even if it breaks due to an external impact, the glass fragments are less likely to scatter. Therefore, it is widely used as windshields, side windows, and rear windows in vehicles such as automobiles, as well as windows in aircraft and buildings.
[0003] As interlayers for laminated glass, vinyl acetal resins obtained by acetalizing polyvinyl alcohol, particularly vinyl butyral resins, are widely used, along with liquid plasticizers. Furthermore, vinyl acetal copolymers modified with α-olefins, obtained by acetalizing α-olefin-vinyl alcohol copolymers, are also being considered for use as interlayers in laminated glass.
[0004] For example, Patent Document 1 describes an interlayer composition for safety laminated glass, mainly composed of an α-olefin-modified polyvinyl acetal resin, which has excellent puncture resistance over a wide temperature range from low to high temperatures. Patent Document 2 describes a vinyl acetal polymer with improved water resistance and improved compatibility with plasticizers, and an interlayer for laminated glass mainly composed of the vinyl acetal polymer. Furthermore, Patent Document 3 describes a sheet made of polyvinyl acetal resin that is easily bonded to glass, has high light transmittance, flexibility, and water vapor barrier properties, and has low water absorption. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Unexamined Patent Publication No. 63-79741 [Patent Document 2] Japanese Patent Publication No. 2004-68013 [Patent Document 3] Japanese Patent Publication No. 2011-57737 [Overview of the project] [Problems that the invention aims to solve]
[0006] In recent years, the performance requirements for laminated glass have increased, and the interlayers used in laminated glass are now required to maintain excellent transparency regardless of the manufacturing conditions of the laminated glass, as well as to have excellent heat resistance and puncture resistance. In particular, regarding heat resistance, there is a demand for even higher heat resistance, such as high self-support even in high-temperature environments, high creep resistance, and the ability to maintain high strength even after a long period of time.
[0007] However, our investigations have shown that sheets containing α-olefin-modified vinyl acetal copolymers, as described in Patent Documents 1 to 3, may not always exhibit sufficient self-supporting properties and creep resistance in high-temperature environments, indicating room for improvement.
[0008] Therefore, the object of the present invention is to provide an acetalized ethylene vinyl alcohol copolymer that can form a resin sheet with excellent self-supporting properties and creep resistance in high-temperature environments while maintaining transparency and puncture resistance, as well as a composition containing the acetalized ethylene vinyl alcohol copolymer. [Means for solving the problem]
[0009] The present inventors, after diligent research to solve the above problems, arrived at the present invention. That is, the present invention encompasses the following preferred embodiments.
[0010] [1] An acetal of an ethylene vinyl alcohol copolymer, Based on the total monomer units constituting the acetal compound, 20-80 mol% ethylene units, and 4-76 mol% vinyl alcohol units Includes, The degree of acetalization is 5-80 mol%, Formula (1): 0.75 ≤ W 0.05h / 2f≦1.00 (1) [In formula (1), W 0.05h / 2f represents the symmetry coefficient determined by reverse-phase partition gradient high-performance liquid chromatography analysis using a water-ethanol eluent, in accordance with JIS K 0124:2011. and equation (2): 1.27 ≤ Tm / Tg ≤ 1.35 (2) [In equation (2), Tm and Tg represent the melting peak temperature (Kelvin) and the midpoint glass transition temperature (Kelvin), respectively, measured in accordance with JIS K7121:2012.] An acetalized ethylene vinyl alcohol copolymer that satisfies the following conditions. [2] An acetalized product of an ethylene vinyl alcohol copolymer, Based on the total monomer units constituting the acetal compound, 20-80 mol% ethylene units, and 4-76 mol% vinyl alcohol units Includes, The degree of acetalization is 5-80 mol%, Formula (1): 0.75 ≤ W 0.05h / 2f≦1.00 (1) [In formula (1), W 0.05h / 2f represents the symmetry coefficient determined by reverse-phase partition gradient high-performance liquid chromatography analysis using a water-ethanol eluent, in accordance with JIS K 0124:2011. Satisfying the conditions, Acetalized ethylene vinyl alcohol copolymer having a meso / racemo ratio of less than 5 in the acetal ring structure. 〔3〕The acetalized product according to 〔1〕, wherein the meso / racemo ratio of the acetal ring structure is less than 5. 〔4〕The SP value is 12.6 (cal / cm 3 ) 1 / 2 The acetalized product according to any one of 〔1〕 to 〔3〕, which is as follows. 〔5〕The acetalized product according to any one of 〔1〕 to 〔4〕, wherein the degree of acetalization is 5 to 62 mol%. 〔6〕The acetalized product (A) according to any one of 〔1〕 to 〔5〕, and at least one component selected from the group consisting of a resin (B) other than the acetalized product (A), a plasticizer, an antioxidant, and an ultraviolet absorber A composition containing the above, wherein the content of the acetalized product (A) is 70% by mass or more. 〔7〕The composition according to 〔6〕, wherein the melting peak temperature Tms measured in accordance with JIS K7121:2012 is 120°C to 180°C. 〔8〕The composition according to 〔6〕 or 〔7〕, wherein the content of the plasticizer is 40 parts by mass or less with respect to 100 parts by mass of the acetalized product (A). 〔9〕The composition according to any one of 〔6〕 to 〔8〕, wherein the content of the plasticizer is 10 to 40 parts by mass with respect to 100 parts by mass of the acetalized product (A). 〔10〕The SP value of the plasticizer is 9.2 to 12.0 (cal / cm 3 ) 1 / 2 The composition according to any one of 〔6〕 to 〔9〕, which is as follows. 〔11〕The resin (B) is an ethylene vinyl alcohol copolymer and / or an acetalized product (B) of an ethylene vinyl alcohol copolymer satisfying the following formula (3): Tm / Tg < 1.27 (3) 〔In formula (3), Tm and Tg respectively represent the melting peak temperature (Kelvin) and the midpoint glass transition temperature (Kelvin) measured in accordance with JIS K7121:2012〕 The composition according to any one of 〔6〕 to 〔10〕, which is an acetalized product (B) of an ethylene vinyl alcohol copolymer satisfying the above. 〔12〕The following formula (4): ΔH AH / ΔH A≤0.30 (4) [In formula (4), ΔH A This represents the heat of fusion of crystals measured using a differential scanning calorimeter (DSC) when the temperature is raised from 25°C to 140°C at a heating rate of 10°C / min, held at 140°C for 30 minutes, then cooled from 140°C to -30°C at a cooling rate of 4°C / min, and then raised again from -30°C to 200°C at a heating rate of 10°C / min, and ΔH AH ΔH A [This shows the heat of fusion on the high-temperature side when the peak is split at 145°C.] A composition according to any one of [6] to
[11] that satisfies the following conditions.
[13] (i) a step of preparing a dispersion containing an ethylene vinyl alcohol copolymer, an aldehyde and a solvent, and impregnating at least a portion of the aldehyde into the ethylene vinyl alcohol copolymer, and (ii) After step (i), a step in which a catalyst is added to the dispersion to convert the ethylene vinyl alcohol copolymer into an acetal. Includes, The ethylene vinyl alcohol copolymer is a porous material. A method for producing an acetalized product according to any one of [1] to [5], wherein the acetalization is carried out by a solid-liquid reaction.
[14] A resin sheet comprising one or more layers containing an acetal compound as described in any of [1] to [5] or a composition as described in any of [6] to
[12] .
[15] An interlayer for laminated glass, made of the resin sheet described in
[14] .
[16] Laminated glass having two glass plates and an interlayer for laminated glass as described in
[15] disposed between the two glass plates. [Effects of the Invention]
[0011] According to the present invention, it is possible to provide an acetalized ethylene vinyl alcohol copolymer that can form a resin sheet with excellent self-supporting properties and creep resistance in high-temperature environments while maintaining transparency and puncture resistance, as well as a composition containing the acetalized copolymer. [Brief explanation of the drawing]
[0012] [Figure 1] Figure 1 shows an example of high-performance liquid chromatography (HPLC) measurement results used to explain the symmetry coefficient. [Figure 2] Figure 2 shows the measurement results obtained by differential scanning calorimeter (DSC) in Example 1. [Modes for carrying out the invention]
[0013] The embodiments of the present invention will be described in detail below. However, the scope of the present invention is not limited to the embodiments described herein, and various modifications can be made without departing from the spirit of the invention. Furthermore, if multiple upper and lower limits are specified for a particular parameter, a suitable numerical range can be obtained by combining any upper and lower limit from among these upper and lower limits.
[0014] [Acetalized ethylene vinyl alcohol copolymer] The acetalized ethylene vinyl alcohol copolymer of the present invention (hereinafter also simply referred to as "acetalized") is of the following formulas (1) and (2): 0.75 ≤ W 0.05h / 2f≦1.00 (1) [In formula (1), W 0.05h / 2f represents the symmetry coefficient determined by reverse-phase partition gradient high-performance liquid chromatography analysis using a water-ethanol eluent, in accordance with JIS K 0124:2011. 1.27 ≤ Tm / Tg ≤ 1.35 (2) [In equation (2), Tm and Tg represent the melting peak temperature (Kelvin) and the midpoint glass transition temperature (Kelvin), respectively, measured in accordance with JIS K7121:2012.] The following conditions are met. Alternatively, the acetal compound of the present invention is given by the following formula (1): 0.75 ≤ W 0.05h / 2f≦1.00 (1) [In formula (1), W 0.05h / 2f represents the symmetry coefficient determined by reverse-phase partition gradient high-performance liquid chromatography analysis using a water-ethanol eluent, in accordance with JIS K 0124:2011. The following conditions are met, and the meso / racemo ratio of the acetal ring structure is less than 5.
[0015] The present inventors have found that both equations (1) and (2) above satisfy the symmetry coefficient W 0.05h When an acetalized ethylene vinyl alcohol copolymer is prepared in which / 2f is 0.75 to 1.00 and the Tm / Tg(K / K) is 1.27 to 1.35, or when the above formula (1) is satisfied, that is, the symmetry coefficient W 0.05h Surprisingly, we have found that by preparing an acetalized ethylene vinyl alcohol copolymer in which the / 2f is 0.75 to 1.00 and the meso / racemo ratio of the acetal ring structure is less than 5, it is possible to improve the self-supporting and creep-resistant properties in high-temperature environments while maintaining the high transparency and puncture resistance of the resin sheet containing the acetalized acetal. In this invention, self-supporting properties in high-temperature environments refer to properties such as the fact that, when the resin sheet is used as an interlayer for laminated glass, even if the glass breaks in a high-temperature environment, the broken glass is less likely to penetrate the resin sheet (interlayer for laminated glass) or the resin sheet is less likely to sag.
[0016] The acetal derivative of the present invention has a symmetry coefficient W determined in accordance with JIS K 0124:2011. 0.05hSince the symmetry coefficient is between 0.75 and 1.00, the transparency of the resulting resin sheet is easily improved. This is thought to be because keeping the symmetry coefficient within the above range imparts an appropriate acetalization degree distribution to the acetalized material. On the other hand, if the symmetry coefficient is outside the above range, the variation in the acetalization degree of the resulting acetalized material increases, and transparency tends to decrease. Furthermore, if the symmetry coefficient exceeds the above upper limit, the proportion of acetalized materials with a high degree of acetalization (high acetalization component) in the resulting acetalized material increases, and transparency tends to decrease. If the symmetry coefficient is below the above lower limit, the proportion of acetalized materials with a low degree of acetalization (low acetalization component) in the resulting acetalized material increases, and transparency and moldability tend to decrease.
[0017] The symmetry coefficient is preferably 0.95 or less, more preferably 0.90 or less, and even more preferably 0.85 or less, from the viewpoint of easily improving transparency. Furthermore, the symmetry coefficient is preferably 0.76 or more, and more preferably 0.77 or more, from the viewpoint of easily improving transparency and moldability. Here, the symmetry coefficient is a coefficient that indicates the degree of symmetry of the measurement peak obtained using high-performance liquid chromatography, and the closer the symmetry coefficient is to 1.0, the higher the symmetry of the peak.
[0018] In the present invention, the symmetry coefficient W 0.05h / 2f can be determined by reverse-phase partition gradient high-performance liquid chromatography analysis using a water-ethanol eluent, in accordance with JIS K 0124:2011. The "W" in the symmetry coefficient is... 0.05h " represents the peak width at 1 / 20th of the peak height from the baseline (5% peak height position) of the measured peak obtained by HPLC analysis, and "f" represents the distance on the rising side of the peak when the peak width at the 5% peak height position is divided by a perpendicular line containing the peak apex. Specifically, in the measured peak in Figure 1, which is an example of the measurement result of high-performance liquid chromatography (HPLC), "W 0.05h " is the peak width W shown in Figure 1.0.05h The coordinate system is shown, and "f" represents the distance f between a and b shown in Figure 1. In Figure 1, a is the starting point at the 5% peak height, and b is the intersection of the horizontal line containing the peak starting point a and the perpendicular line containing the peak apex. Also in Figure 1, the dotted line parallel to the horizontal axis represents the baseline.
[0019] The above HPLC analysis can typically be performed under the following measurement conditions. Sample concentration: 1.5 mg / 1 g Sample solvent: Ethanol (99.5%) / Ion-exchanged water = 9 / 1 wt% mixed solvent Injection volume: 20μL Detector: Varian 380-LC, EVAP 80°C (pre-stage heating), NEB 50°C (second stage heating), Gas 1.5 (SLM), data acquisition interval 1000 msec, filter 1 μm ODS Silica Column: Shimadzu Corporation's "Shimpack G-ODS (Octadecyl group modified spherical fully porous silica gel, inner diameter 4 mm x length 10 mm, particle size 5 μm)" Column temperature: 45℃ Fluid delivery rate: Total flow rate 0.4 mL / min
[0020] Furthermore, the HPLC analysis of the present invention can be performed by the following procedure. Different types of liquids with different polarities are used as mobile phases. Water is used as mobile phase A, and ethanol (99.5%) is used as mobile phase B. Before sample injection, the inside of the HPLC system column is filled with a mixed solvent of mobile phase A / mobile phase B in a volume ratio of 95 / 5. The sample is injected in this state. Then, the solvent is flowed under the following conditions. 0~5 minutes (B concentration;_5% constant) 5~25 minutes (B concentration;_5~100%) 25~30 minutes (B concentration; 100% constant) 30~31 minutes (B concentration; 100~5%) 31~55 minutes (B concentration;_5% constant)
[0021] The symmetry coefficient can be adjusted by appropriately adjusting the distribution of the degree of acetalization in the acetalized product and / or the manufacturing conditions of the acetalized product. For example, the symmetry coefficient may be adjusted to the above range by selecting a method for producing an acetalized product of ethylene vinyl alcohol copolymer, as described later, particularly an acetalization method described as a preferred embodiment in the description below.
[0022] The acetalized material of the present invention has a melting peak temperature (Kelvin) to midpoint glass transition temperature (Kelvin) ratio Tm / Tg of 1.27 to 1.35, measured in accordance with JIS K7121:2012, and / or a meso / racemo ratio of the acetal ring structure of less than 5. Therefore, it is possible to improve the self-supporting and creep resistance in high-temperature environments while maintaining the transparency of the resulting resin sheet. This is because, while higher crystallinity generally improves self-supporting and creep resistance in high-temperature environments, it tends to decrease transparency. However, by keeping the Tm / Tg of the acetalized material within the above range, or by keeping the meso / racemo ratio of the acetal ring structure of less than 5, an appropriate level of crystallinity is imparted to the acetalized material that allows for both transparency and self-supporting and creep resistance in high-temperature environments. On the other hand, if Tm / Tg(K / K) exceeds the above upper limit, transparency tends to decrease, and if it is below the above lower limit, self-supporting and creep resistance in high-temperature environments tend to decrease. Also, if the meso / racemo ratio of the acetal ring structure is 5 or higher, self-supporting and creep resistance in high-temperature environments tend to decrease.
[0023] The Tm / Tg(K / K) is 1.35 or less, preferably 1.33 or less, more preferably 1.31 or less, and even more preferably 1.30 or less, from the viewpoint of easily improving transparency. Furthermore, the Tm / Tg(K / K) is 1.27 or more, preferably 1.275 or more, and more preferably 1.28 or more, from the viewpoint of easily improving self-supporting and creep resistance in high-temperature environments, and easily improving puncture resistance. The Tm / Tg(K / K) can be determined by measuring the melting peak temperature (Kelvin) and the midpoint glass transition temperature (Kelvin) in accordance with JIS K7121:2012 using a differential scanning calorimeter (DSC). Alternatively, it may be determined by measuring the melting peak temperature Tm(°C) and the midpoint glass transition temperature Tg(°C) and converting these values to Kelvin (K), or, for example, by the method described in the examples.
[0024] In the acetalized product of the present invention, the melting peak temperature Tm (°C), measured in accordance with JIS K7121:2012, is preferably 120°C or higher, more preferably 125°C or higher, even more preferably 130°C or higher, and also preferably 180°C or lower, more preferably 175°C or lower, even more preferably 170°C or lower, even more preferably 160°C or lower, and particularly preferably 150°C or lower. When the melting peak temperature Tm is above the lower limit, it is easier to improve self-supporting properties and creep resistance in high-temperature environments, and when it is below the upper limit, it is easier to improve transparency and moldability.
[0025] In the acetalized product of the present invention, the intermediate glass transition temperature Tg (°C), measured in accordance with JIS K7121:2012, is preferably 20°C or higher, more preferably 30°C or higher, even more preferably 40°C or higher, and also preferably 80°C or lower, more preferably 60°C or lower, and even more preferably 50°C or lower. If the intermediate glass transition temperature Tg is above the lower limit, it is easier to improve moldability (e.g., film-forming ability), and if it is below the upper limit, it is easier to improve the puncture resistance of the resulting resin sheet.
[0026] The Tm / Tg(K / K) can be adjusted by appropriately adjusting the distribution of the degree of acetalization in the acetalized product and / or the manufacturing conditions of the acetalized product. For example, the Tm / Tg(K / K) can be adjusted to the above range by selecting a method for producing an acetalized product of an ethylene vinyl alcohol copolymer described later, particularly an acetalization method described as a preferred embodiment in the description below.
[0027] In the present invention, the meso / racemo ratio of the acetal ring structure is the ratio of the amount of acetal groups having a mesoacetal ring to the amount of acetal groups having a racemoacetal ring in the stereostructure of the acetal ring. The racemoacetal ring is an acetal ring structure formed from hydroxyl groups having a syndiotactic structure, and the mesoacetal ring is an acetal ring structure formed from hydroxyl groups having an isotactic structure. The meso / racemo ratio is preferably less than 5, more preferably 4 or less, even more preferably 3 or less, even more preferably 2.5 or less, and particularly preferably 2 or less, from the viewpoint of easily improving transparency and self-supporting and creep resistance in high-temperature environments. From the viewpoint of productivity, it is preferably 1.0 or more, more preferably 1.2 or more, and even more preferably 1.4 or more. When the meso / racemo ratio is less than or equal to the above upper limit, the number of syndiotactic hydroxyl groups is relatively reduced, and a moderate crystallinity is imparted to the acetal derivative that can achieve both transparency and self-supporting and creep resistance in high-temperature environments. Thus, it is possible to improve self-supporting and creep resistance in high-temperature environments while maintaining transparency. In addition, the relative reduction of syndiotactic hydroxyl groups reduces hydrogen bonding between hydroxyl groups, improving the compatibility of plasticizers. The meso / racemo ratio can be determined by performing a 13C-NMR measurement and calculating the intensity ratio of the peak originating from the methine C atom of the acetal portion of the meso-type 6-membered butyral ring and the peak originating from the methine C atom of the acetal portion of the racemo-type 6-membered butyral ring from the obtained spectrum. This can be determined, for example, by the method described in the examples.
[0028] The meso / racemo ratio can be adjusted by appropriately adjusting the degree of acetalization of the acetalized product, the reaction time, the reaction mode, and other conditions for producing the acetalized product. For example, the meso / racemo ratio may be adjusted to the above range by selecting a method for producing an acetalized product of ethylene vinyl alcohol copolymer, as described later, particularly an acetalization method described as a preferred embodiment in the later description.
[0029] The ethylene unit content of the acetalized product of the present invention is 20 to 80 mol% relative to the total monomer units constituting the acetalized product. When the ethylene unit content is within the above range, it is easier to improve the puncture resistance and self-supporting properties of the resulting resin sheet, particularly its self-supporting properties under high-temperature environments, as well as the moldability of the acetalized product. The ethylene unit content may be preferably 25 mol% or more, more preferably 30 mol% or more, and even more preferably 35 mol% or more, from the viewpoint of improving the puncture resistance and transparency of the resulting resin sheet, as well as the moldability of the acetalized product. Furthermore, from the viewpoint of increasing the storage modulus and improving the self-supporting properties of the resulting resin sheet, it may be preferably 60 mol% or less, more preferably 55 mol% or less, and even more preferably 50 mol% or less.
[0030] The vinyl alcohol unit content of the acetalized product of the present invention is 4 to 76 mol% relative to the total monomer units constituting the acetalized product. When the vinyl alcohol unit content is within the above range, the transparency and adhesion to substrates such as glass of the resulting resin sheet are easily enhanced. The content of the vinyl alcohol units may be preferably 10 mol% or more, more preferably 20 mol% or more, even more preferably 25 mol% or more, and particularly preferably 30 mol% or more, relative to the total unit content of the acetal, from the viewpoint of easily improving adhesion to substrates such as glass. Furthermore, from the viewpoint of easily improving the transparency of the resulting acetal, it may be preferably 70 mol% or less, more preferably 65 mol% or less, even more preferably 60 mol% or less, and particularly preferably 55 mol% or less.
[0031] The content of acetal units (acetalized vinyl alcohol units) in the acetalized product of the present invention may be preferably 1 mol% or more, more preferably 3 mol% or more, even more preferably 5 mol% or more, even more preferably 10 mol% or more, and particularly preferably 15 mol% or more, relative to the total monomer units constituting the acetalized product, from the viewpoint of keeping the crystallinity of the acetalized product low and easily increasing transparency. Furthermore, from the viewpoint of easily increasing self-supporting properties, particularly self-supporting properties in high-temperature environments, creep resistance in high-temperature environments, and adhesion to substrates such as glass, it may be preferably 70 mol% or less, more preferably 60 mol% or less, even more preferably 55 mol% or less, even more preferably 50 mol% or less, and particularly preferably 45 mol% or less.
[0032] The acetal product of the present invention may contain vinyl ester units such as vinyl acetate units, and the content of vinyl ester units may be preferably 0 to 5 mol%, more preferably 0 to 2 mol%, and even more preferably 0 to 1 mol%, from the viewpoint of heat decomposition resistance.
[0033] The acetalized product of the present invention may contain other monomer units in addition to ethylene units, vinyl alcohol units, and acetal units, and optionally vinyl ester units, to the extent that it does not impair the effects of the present invention. Examples of other monomer units include α-olefins such as propylene, isobutylene, α-octene, and α-dodecene; unsaturated acids such as acrylic acid, methacrylic acid, methyl methacrylate, crotonic acid, maleic acid, and itaconic acid, or their anhydrides, salts, or mono- or dialkyl esters; nitriles such as acrylonitrile and methacrylonitrile; amides such as acrylamide and methacrylamide; olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid, or their salts; alkyl vinyl ethers, vinyl ketones, N-vinylpyrrolidone, vinyl chloride, and vinylidene chloride. When the ethylene vinyl alcohol copolymer contains other monomer units, their content is preferably 15 mol% or less, more preferably 10 mol% or less.
[0034] The content of each unit in the acetalized product can be determined by NMR measurement, for example, by the method described in the examples.
[0035] The degree of acetalization of the acetalized product is 5 to 80 mol%. When the degree of acetalization is within the above range, it is easier to improve the transparency, self-supporting properties, self-supporting properties and creep resistance in high-temperature environments, and adhesion to substrates such as glass of the resulting resin sheet. From the viewpoint of keeping the crystallinity of the acetalized product low and easily improving transparency, the degree of acetalization may be preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 15 mol% or more, even more preferably 20 mol% or more, and particularly preferably 25 mol% or more. Furthermore, from the viewpoint of easily improving self-supporting properties and creep resistance in high-temperature environments, and adhesion to substrates such as glass, it may be preferably 70 mol% or less, more preferably 62 mol% or less, even more preferably 60 mol% or less, even more preferably 50 mol% or less, and particularly preferably 40 mol% or less. In this invention, the degree of acetalization refers to the ratio of acetal units to the total content of acetal units, vinyl alcohol units, and vinyl ester units such as vinyl acetate units in the acetalized product. Specifically, in this invention, the degree of acetalization is given by the following formula, where k is the content of acetal units, l is the content of vinyl alcohol units, and m is the content of vinyl ester units: Acetalization degree (mol %) = {k / (k+l+m)} × 100 This can be determined by [method].
[0036] In one embodiment of the present invention, the SP value (solubility parameter) of the acetal compound is preferably 12.6 (cal / cm³). 3 ) 1 / 2 More preferably 12.4 (cal / cm 3 ) 1 / 2 More preferably, 12.2 (cal / cm 3 ) 1 / 2 More preferably, 12.0 (cal / cm 3 ) 1 / 2 The following, and preferably 10.8 (cal / cm³) 3 ) 1 / 2 More preferably 11.0 (cal / cm²) 3 ) 1 / 2 More preferably 11.2 (cal / cm²) 3 ) 1 / 2 That concludes the explanation. When the SP value is below the upper limit and / or above the lower limit, it is easier to suppress plasticizer bleed-out when a plasticizer is added to the acetal compound of the present invention to prepare a composition. The SP value is calculated according to Fedors' calculation method (RFFedors, Polym.Eng.Sci., 14, 147 (1947)).
[0037] In a preferred embodiment of the present invention, the resin sheet obtained from the acetalized product of the present invention exhibits values similar to those of the resin sheet of the present invention described in the [Resin Sheet] section below, including haze, slow-cooling haze, storage modulus, relaxation modulus, and penetration energy. Therefore, the acetalized product of the present invention can form a resin sheet with excellent transparency, penetration resistance, and superior self-supporting and creep resistance in high-temperature environments. Furthermore, in a preferred embodiment of the present invention, the acetal product of the present invention is as described in the section [Composition], with a melting peak temperature Tms, melt flow rate (MFR), and ΔH AH / ΔH A It shows a similar value to [the previous example].
[0038] [Method for producing acetalized ethylene vinyl alcohol copolymers] The method for producing the acetalized product of the present invention is not particularly limited, but for example, (i) a step of preparing a dispersion containing an ethylene vinyl alcohol copolymer, an aldehyde and a solvent, and impregnating at least a portion of the aldehyde into the ethylene vinyl alcohol copolymer, and (ii) After step (i), a step in which a catalyst is added to the dispersion to convert the ethylene vinyl alcohol copolymer into an acetal. Includes, The ethylene vinyl alcohol copolymer is a porous material. This can be produced by carrying out the acetalization by a solid-liquid reaction.
[0039] <Process (i)> Step (i) is a step of preparing a dispersion (hereinafter also referred to as "EVOH dispersion") containing ethylene vinyl alcohol copolymer (hereinafter also referred to as "EVOH"), an aldehyde, and a solvent, and impregnating at least a portion of the aldehyde into the ethylene vinyl alcohol copolymer.
[0040] In the method of the present invention, the EVOH contained in the EVOH dispersion is a porous material. By using a porous material of ethylene vinyl alcohol copolymer (hereinafter also referred to as "EVOH porous material" or simply "porous material") as a raw material, it is easy to uniformly acetalize EVOH, and it is easy to adjust the symmetry coefficient of the resulting acetalized product within the above range. Therefore, even if solid EVOH is acetalized by a heterogeneous method, intermolecular crosslinking of EVOH is less likely to occur, and an acetalized product with excellent transparency can be obtained. This is thought to be because, by using an EVOH porous material, when at least a portion of the aldehyde described later is impregnated into the EVOH, the aldehyde, which is the acetalizing agent, penetrates not only the solid surface of EVOH but also into the solid interior of EVOH through the pores, thereby enabling uniform acetalization of EVOH. As a result, the difference in the degree of acetalization between the solid surface and the solid interior of the acetalized product obtained by acetalization becomes small, and an acetalized product with a narrow distribution of acetalization degree can be obtained.
[0041] In the present invention, the EVOH porous body is preferably EVOH having a large number of pores, and it is preferable that some or all of the pores have openings on the surface of the porous body.
[0042] In one embodiment of the present invention, the median diameter of the pores in the EVOH porous body is preferably 0.005 μm or more, more preferably 0.01 μm or more, and even more preferably 0.02 μm or more, from the viewpoint of uniformly acetalizing EVOH and improving the transparency of the resulting EVOH acetal product. Furthermore, the median diameter is preferably 1 μm or less, more preferably 0.5 μm or less, even more preferably 0.2 μm or less, even more preferably less than 0.2 μm, particularly preferably 0.18 μm or less, particularly more preferably 0.15 μm or less, and especially preferably 0.12 μm or less, from the viewpoint of the porous body being less likely to collapse into powder during the manufacturing process of the EVOH acetal product, thus reducing the likelihood of blockage of the manufacturing line and facilitating efficient production of the acetal product. The median diameter of a pore is the median diameter (d50) for all pores in the logarithmic differential pore volume (Log differential pore volume) distribution within the range of pore diameters from 0.005 to 100 μm. The reason for limiting the pore diameter range to 0.005 to 100 μm in the pore distribution is that pores larger than 100 μm mainly consist of interparticle voids, while pores smaller than 0.005 μm (near the lower limit of measurement) include pseudopores caused by compression, etc.
[0043] The median diameter of the pores in a porous material can be adjusted by the manufacturing conditions of the porous material. For example, when an EVOH porous material is manufactured by preparing a composition containing EVOH and at least one solvent selected from water and alcohol, extruding the composition in a strand shape into a solidifying solution to solidify it, and then cutting the resulting strand-shaped solid, the median diameter of the porous material can be adjusted by the type and amount of solvent contained in the composition, the linear velocity when extruding the composition, the extrusion temperature, and the cooling rate. Furthermore, the median diameter of these pores can be measured using a pore distribution measuring device, for example, by the method described in the examples.
[0044] In one embodiment of the present invention, it is preferable that the porous EVOH body has pores at its center of gravity. Having pores at its center of gravity allows the aldehyde to penetrate into the solid interior of the EVOH, particularly to its center of gravity. As a result, the EVOH can be uniformly acetalized, making it less likely for intermolecular crosslinking of the EVOH to occur and improving the transparency of the resulting EVOH acetal. In the present invention, having pores at the center of gravity of a porous body means that, in a cross-section of the porous body passing through its center of gravity, when the shortest distance L is the distance from the center of gravity of the cross-section to the surface of the porous body, pores exist in a region within 50% of the distance L from the center of gravity of the cross-section.
[0045] In one embodiment of the present invention, the EVOH porous body is preferably configured such that, from the viewpoint of uniformly acetalizing EVOH and easily improving the transparency of the resulting acetalized EVOH, when the shortest distance L from the centroid of the porous body to the surface of the porous body is defined as the distance L, the porous body has pores in a region preferably within 30%, more preferably within 20%, and even more preferably within 10% of the distance L from the centroid of the cross-section.
[0046] In one embodiment of the present invention, the total pore area in the cross-section of the porous body passing through the center of gravity of the EVOH porous body is preferably 10 area % or more, more preferably 20 area % or more, and even more preferably 30 area % or more, of the total cross-sectional area, from the viewpoint of uniformly acetalizing the EVOH and improving the transparency of the resulting acetalized EVOH. Furthermore, the total pore area may be preferably 60 area % or less, more preferably 50 area % or less, of the total cross-sectional area, from the viewpoint of increasing the strength of the porous body, making it less likely for the porous body to collapse during the manufacturing process of the acetalized product, and facilitating efficient production of the acetalized product.
[0047] A cross-section of the EVOH porous material passing through its center of gravity can be prepared using a single-edged razor or the like. Furthermore, the presence or absence of pores in this cross-section and the proportion of the total pore area can be confirmed and calculated by observing and analyzing electron microscope images of the cross-section.
[0048] In one embodiment of the present invention, the pore surface area (specific surface area) of the EVOH porous body in the range of 0.005 to 100 μm, measured by the mercury intrusion method, is preferably 25 μm, from the viewpoint of easily improving the transparency of the EVOH acetal. 2 / g or more, comfortably within 30m 2 It is 1 / g or more. Furthermore, the surface area of the pores of the EVOH porous body is preferably 45m², from the viewpoint of easily suppressing adhesion between EVOH porous bodies during high-temperature washing in the manufacturing process of the EVOH porous body. 2 / g or less, more preferably 41m 2 / g or less, more preferably 39m 2 It is less than / g. The pore surface area of the EVOH porous material in the 0.005 to 100 μm range can be adjusted by the manufacturing conditions of the porous material. For example, similar to the method for adjusting the median diameter of the pores of the porous material, it can be adjusted by the type and content of solvent contained in the composition, the linear velocity when extruding the composition into the solidification solution, the extrusion temperature, and the cooling rate. Furthermore, the pore surface area of the EVOH porous material can be measured using a pore distribution measuring device.
[0049] In one embodiment of the present invention, the pore volume of the EVOH porous body may be preferably 0.1 mL / g or more, more preferably 0.2 mL / g or more, and even more preferably 0.25 mL / g or more, from the viewpoint of uniformly acetalizing EVOH and improving the transparency of the resulting acetalized EVOH product. Furthermore, the pore volume may be preferably 1.0 mL / g or less, more preferably 0.5 mL / g or less, and even more preferably 0.3 mL / g or less, from the viewpoint of ease of handling. The pore volume of the EVOH porous material can be adjusted by the manufacturing conditions of the porous material. For example, similar to the method for adjusting the median diameter of the pores of the porous material, it can be adjusted by the type and amount of solvent contained in the composition, the linear velocity when extruding the composition into the solidification solution, the extrusion temperature, and the cooling rate during solidification. Furthermore, the pore volume of the porous material can be measured using a pore distribution measuring device.
[0050] In one embodiment of the present invention, the average particle size of the EVOH porous body may be preferably 1 mm or more, more preferably 2 mm or more, and even more preferably 3 mm or more, from the viewpoint of ease of handling. Furthermore, the average particle size may be preferably 10 mm or less, more preferably 7 mm or less, and even more preferably 5 mm or less, from the viewpoint of facilitating uniform acetalization of EVOH and improving the transparency of the resulting acetalized product. The average particle size can be measured, for example, by the method described in the examples.
[0051] The shape of the EVOH porous body is not particularly limited and can be in the form of powder, pellets, flakes, beads, or irregular shapes. Among these, the porous body is preferably in the form of powder or pellets, and more preferably in the form of pellets. In this invention, a pellet-shaped porous body refers to a solid porous body having a substantially constant size, such as a spherical, cylindrical, elliptical prism, or polygonal prism, and its cross-section may be circular, elliptical, polygonal, etc.
[0052] In the present invention, when the EVOH porous body is in pellet form, the pellet-shaped porous body can be produced by methods such as extruding an ethylene vinyl alcohol copolymer composition into a solidification liquid to solidify it into strands, and then cutting the resulting strand-shaped solidified material to a predetermined length with a strand cutter or the like, or by directly cutting the ethylene vinyl alcohol copolymer composition in a molten state, as described below.
[0053] Examples of ethylene vinyl alcohol copolymers include those obtained by copolymerizing ethylene with a vinyl ester monomer and saponifying the resulting copolymer. In one embodiment of the present invention, the ethylene content of the ethylene vinyl alcohol copolymer (hereinafter also referred to as the ethylene unit content) is preferably 20 to 80 mol% with respect to the total monomer units constituting EVOH. Furthermore, from the viewpoint of easily improving the puncture resistance and moldability of the resulting acetal, the ethylene content may be more preferably 25 mol% or more, even more preferably 30 mol% or more, and particularly preferably 35 mol% or more. Also, from the viewpoint of easily improving the self-supporting properties of the resulting acetal, it may be more preferably 60 mol% or less, even more preferably 55 mol% or less, and particularly preferably 50 mol% or less.
[0054] The degree of saponification of EVOH is not particularly limited, but from the viewpoint of heat decomposition resistance, for example, it is preferably 95 mol% or more, more preferably 98 mol% or more, even more preferably 99 mol% or more, and particularly preferably 99.9 mol% or more. The upper limit of the degree of saponification is not particularly limited and may be, for example, 100 mol% or less.
[0055] The content of vinyl alcohol units in the ethylene vinyl alcohol copolymer may be preferably 40 mol% or more, more preferably 45 mol% or more, and even more preferably 50 mol% or more, relative to the total monomer units constituting EVOH, from the viewpoint of easily improving the self-supporting properties of the resulting acetalized product. Furthermore, from the viewpoint of easily improving the puncture resistance and moldability of the resulting acetalized product, the content may be preferably 80 mol% or less, more preferably 75 mol% or less, even more preferably 70 mol% or less, and particularly preferably 65 mol% or less.
[0056] In the present invention, the ethylene vinyl alcohol copolymer may contain, in addition to ethylene units, vinyl alcohol units, and vinyl ester units, monomer units derived from monomers copolymerizable with these units (hereinafter also referred to as other monomer units), to the extent that the effects of the present invention are not impaired. Examples of the other monomer units include monomer units similar to those that may be contained in the acetalized product. When the ethylene vinyl alcohol copolymer contains other monomer units, the content thereof is preferably 15 mol% or less, more preferably 10 mol% or less.
[0057] The content of ethylene units, vinyl alcohol units, and optionally other monomer units in EVOH in the present invention can be determined by NMR measurement, for example, by the method described in the examples.
[0058] The copolymerization form of the ethylene vinyl alcohol copolymer is not particularly limited and may be any of the following: random copolymer, alternating copolymer, block copolymer, graft copolymer, etc.
[0059] In one embodiment of the present invention, the melt flow rate (MFR) of the ethylene vinyl alcohol copolymer, measured in accordance with JIS K7210-1:2014 under conditions of 190°C and 2.16 kg, may preferably be 1 to 30 g / 10 min, more preferably 2 to 20 g / 10 min, and even more preferably 3 to 10 g / 10 min, from the viewpoint of easily suppressing thermal degradation of the resulting acetalized product during molding.
[0060] The method for producing the porous ethylene vinyl alcohol copolymer is not particularly limited and can be produced by known methods. As an example, a method for producing a pellet-shaped porous EVOH material will be described.
[0061] Pellet-shaped porous EVOH materials can be manufactured by, for example, the steps described in Japanese Patent Publication No. 11-293077 and Japanese Patent Publication No. 2002-121290, which involve preparing a composition containing an ethylene vinyl alcohol copolymer and at least one solvent selected from water and alcohol, extruding the composition in strand form into a solidification liquid, allowing it to solidify, and then cutting it, or by directly cutting the composition in a molten state.
[0062] The EVOH contained in the above composition can be obtained by copolymerizing ethylene with a vinyl ester monomer and saponifying the resulting copolymer. Examples of vinyl ester monomers used as raw materials for EVOH include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl caprylate, vinyl laurylate, vinyl palmitate, vinyl stearate, vinyl oleate, and vinyl benzoate. Among these, vinyl acetate is preferred. The method for copolymerizing ethylene and vinyl ester monomers is not particularly limited and may be carried out by conventionally known methods, such as solution polymerization, bulk polymerization, suspension polymerization, emulsion polymerization, etc. The polymerization initiator that can be used in the copolymerization is a conventionally known polymerization initiator such as azo initiators, peroxide initiators, redox initiators, etc., which can be appropriately selected depending on the polymerization method. Saponification of copolymerization between ethylene and vinyl ester monomers can be carried out by conventionally known methods such as alcohol decomposition or hydrolysis using alkaline or acidic catalysts. Among these methods, saponification using methanol as a solvent and caustic soda (NaOH) as a catalyst is preferred because it is simple.
[0063] The alcohol that may be included in the above composition is not particularly limited as long as it is a solvent that can dissolve EVOH, and examples include methanol, ethanol, propanol, isopropanol, etc. Among these alcohols, alcohols with a boiling point of 100°C or lower are preferred because they have a low boiling point and are easy to remove, and methanol is particularly preferred.
[0064] If the composition contains water as a solvent, it may be prepared by directly adding water to EVOH or to a composition containing EVOH and alcohol. Alternatively, it may be prepared by concentrating an EVOH alcohol solution obtained by dissolving EVOH in alcohol, and then adding water to the EVOH alcohol solution in an amount that does not cause EVOH to precipitate. Alternatively, water vapor may be introduced into EVOH or a composition containing EVOH and alcohol, and at least some of the alcohol may be discharged along with the water vapor to obtain a composition containing EVOH and water, or EVOH, water and alcohol.
[0065] The alcohol that can be used to prepare the EVOH alcohol solution is not particularly limited as long as it is a solvent that can dissolve EVOH, and examples include alcohols similar to those that can be contained in the above composition. Alcohols with a boiling point of 100°C or lower are preferred, and methanol is particularly preferred, because they have a low boiling point and are easy to remove. The alcohol content in the EVOH alcohol solution may be preferably 1 to 500 parts by mass, more preferably 5 to 200 parts by mass, per 100 parts by mass of EVOH.
[0066] When the composition contains water, the water content is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 50 parts by mass or more, per 100 parts by mass of EVOH, from the viewpoint of easily uniformly acetalizing EVOH and easily removing the neutralized salt produced by neutralization after the acetalization reaction. Furthermore, from the viewpoint of easily increasing the strength of the resulting porous body and thus easily producing acetalized products, the water content is preferably 500 parts by mass or less, more preferably 300 parts by mass or less, and even more preferably 200 parts by mass or less.
[0067] When the composition contains alcohol, the alcohol content is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, and even more preferably 50 parts by mass or more, per 100 parts by mass of EVOH, from the viewpoint of easily uniformly acetalizing EVOH and easily removing the neutralized salt produced by neutralization after the acetalization reaction. Furthermore, from the viewpoint of easily increasing the strength of the resulting porous body and thus easily producing acetalized products, the alcohol content is preferably 500 parts by mass or less, more preferably 300 parts by mass or less, and even more preferably 200 parts by mass or less.
[0068] The coagulation solution used to solidify the aforementioned composition is not particularly limited as long as it is a solvent capable of solidifying EVOH, but it is preferable to use water, alcohol, or a mixed solvent of water and alcohol as the coagulation solution.
[0069] The temperature of the coagulation solution is preferably 0 to 50°C, more preferably 0 to 30°C, from the viewpoint of easily coagulating the composition sufficiently. Furthermore, the temperature of the composition when it is extruded into the coagulation solution is preferably 90 to 150°C, more preferably 100 to 140°C, from the viewpoint of the fluidity of EVOH. As described above, by extruding the composition into a solidification solution and allowing it to solidify, the resulting solidified body becomes a porous body with oriented pores.
[0070] The resulting strand-like solidified material can be cut, for example, using a strand cutter. By cutting the resulting strand-like solidified material with a strand cutter, pellet-shaped EVOH porous material can be obtained.
[0071] One method for obtaining a pellet-shaped EVOH porous body by directly cutting the aforementioned composition in a molten state is to obtain a pellet-shaped EVOH porous body by extruding the molten material of the aforementioned composition from an extruder using a hot-cut method or a hot-cut method in water. As described above, by extruding and pelletizing the molten material of the composition, the resulting pellets become porous bodies with oriented pores.
[0072] The method for producing the powdered EVOH porous body is not particularly limited, and for example, it may be obtained by crushing the pelletized porous body obtained by the above method using a pulverizer or the like.
[0073] The EVOH porous body may contain a solvent, but if the solvent is a good solvent for EVOH, it is preferable that the amount of good solvent in the EVOH is reduced by drying or other means to the extent that the pores of the EVOH porous body do not become clogged. If the solvent is a poor solvent for EVOH such as water, the EVOH porous body may contain 5 to 200 parts by mass of the poor solvent such as water per 100 parts by mass of the EVOH porous body.
[0074] In one embodiment of the present invention, the EVOH content in the EVOH dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less, based on the total mass of the dispersion.
[0075] The aldehyde contained in the EVOH dispersion is not particularly limited, but examples include formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde, hexylaldehyde, benzaldehyde, isobutyraldehyde, 2-ethylhexylaldehyde, 2-methylbutyraldehyde, trimethylacetaldehyde, 2-methylpentylaldehyde, 2,2-dimethylbutyraldehyde, 2-ethylbutyraldehyde, and 3,5,5-trimethylhexylaldehyde. These aldehydes may be used individually or in combination of two or more. In one embodiment of the present invention, the aldehyde is preferably butyraldehyde, benzaldehyde, or isobutyraldehyde, with isobutyraldehyde being more preferred, from the viewpoint of improving the self-supporting properties, creep resistance, and transparency of the resulting acetal product in high-temperature environments. Furthermore, in one embodiment of the present invention, from the viewpoint of easily improving the transparency of the resulting acetal, it is preferable that the aldehyde does not have a carboxyl group.
[0076] The aldehyde content in the EVOH dispersion is not particularly limited and can be adjusted as appropriate according to the desired degree of acetalization. In one embodiment of the present invention, the aldehyde content may be preferably 1 to 40 parts by mass, more preferably 5 to 35 parts by mass, and even more preferably 10 to 30 parts by mass, per 100 parts by mass of EVOH, from the viewpoint of easily improving the transparency and impact resistance of the resulting acetalized product.
[0077] Since the method of the present invention carries out acetalization by a solid-liquid reaction, the solvent contained in the EVOH dispersion is a poor solvent for EVOH and its acetal derivative, preferably a solvent containing water, and more preferably water.
[0078] The method for preparing the EVOH dispersion is not particularly limited. For example, it may be prepared by adding an aldehyde to a dispersion in which EVOH is dispersed in a solvent, or by adding a solvent to a mixture of EVOH and an aldehyde.
[0079] In the method of the present invention, after preparing the EVOH dispersion, at least a portion of the aldehyde is impregnated into the ethylene vinyl alcohol copolymer before adding the catalyst. This impregnates the aldehyde into the EVOH, allowing for uniform acetalization of the EVOH. As a result, the symmetry coefficient of the resulting acetalized product can be easily adjusted within the above range, and its transparency can be easily improved.
[0080] The temperature at which the aldehyde is impregnated into the EVOH is not particularly limited, but from the viewpoint of enabling faster impregnation of the aldehyde into the EVOH, it may be, for example, 20°C or higher, preferably 30°C or higher, more preferably 40°C or higher, and even more preferably 50°C or higher. Furthermore, from the viewpoint of suppressing fusion of EVOH molecules, it may be preferably 100°C or lower, more preferably 90°C or lower, and even more preferably 80°C or lower.
[0081] The time for impregnating the aldehyde into EVOH can be appropriately selected depending on the impregnation temperature and the pore structure of the EVOH porous body, and is preferably 10 minutes or more, more preferably 30 minutes or more, and even more preferably 60 minutes or more. There is no particular upper limit, and it may be, for example, 10 hours.
[0082] <Process (ii)> Step (ii) is a step in which an aldehyde is impregnated into EVOH, and then a catalyst is added to the EVOH dispersion prepared in step (i) to acetalize the EVOH. In the method of the present invention, the acetalization is carried out by a solid-liquid reaction. By carrying out the acetalization by a solid-liquid reaction, it is easy to adjust the Tm / Tg (K / K) of the resulting acetalized product to within the above range, and it is also easy to adjust the meso / racemo ratio of the acetal ring structure of the acetalized product to within the above range, thereby improving self-supporting properties and creep resistance in high-temperature environments while maintaining transparency. Furthermore, by carrying out the acetalization by a solid-liquid reaction, the generated acetalized product can be separated from the reaction solution by filtration, making it easy to efficiently produce the acetalized product and to produce the acetalized product in high yield. In this invention, the method of acetalization by a solid-liquid reaction (hereinafter also referred to as the "solid-liquid method") refers to a method in which EVOH and the acetalized EVOH produced by acetalization are used as poor solvents for the acetalization reaction, thereby obtaining the resulting acetalized EVOH as a solid dispersed in a dispersion without dissolving EVOH and the acetalized EVOH in the solvent during the acetalization step.
[0083] The catalyst for acetalization is not particularly limited and may be an inorganic or organic acid. Examples of acidic catalysts include acetic acid, p-toluenesulfonic acid, nitric acid, sulfuric acid, hydrochloric acid, phosphoric acid, and carbonic acid. Among these catalysts, inorganic acids such as hydrochloric acid, sulfuric acid, and nitric acid are preferred because they easily increase the reaction rate of the acetalization reaction, facilitate washing from the resulting acetalized product, and allow for efficient production of the acetalized product.
[0084] The amount of catalyst added to the EVOH dispersion can be appropriately selected depending on the type of catalyst and the reaction temperature. For example, the catalyst concentration in the EVOH dispersion may be preferably 0.001 to 1.0 mol / L, more preferably 0.01 to 0.8 mol / L, and even more preferably 0.05 to 0.5 mol / L.
[0085] The method of adding the catalyst to the EVOH dispersion is not particularly limited; for example, the catalyst may be added to the EVOH dispersion all at once, or it may be added in multiple steps. From the viewpoint of obtaining an acetalized product with low haze and excellent transparency, it is preferable to add the catalyst to the EVOH dispersion in multiple steps, and particularly preferable to add it in two steps. When the catalyst is added to the EVOH dispersion in multiple stages, the amount of the first addition of catalyst is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less, relative to the total amount added. If the amount of the first addition of catalyst is below the above upper limit, the distribution of the degree of acetalization becomes narrower, making it easier to improve the transparency of the resulting acetal product.
[0086] The reaction temperature for acetalization is preferably below the glass transition temperature of EVOH, from the viewpoint of easily maintaining the pores of the EVOH porous material. The reaction temperature may more preferably be 10 to 80°C, more preferably 20 to 70°C, and even more preferably 30 to 60°C. Furthermore, acetalization may be carried out in air, in an inert gas such as nitrogen gas or argon gas, and may be carried out under normal pressure, under pressurized pressure, or under reduced pressure.
[0087] After the acetalization reaction, the resulting reaction solution may be neutralized with an alkali as needed, and then the acetalized product may be separated and purified from the reaction solution by conventional separation methods, such as filtration, concentration, reprecipitation, and recrystallization. It is preferable to remove the neutralized salt produced by neutralization by washing or the like. The alkali that can be used for neutralization is not particularly limited and examples include sodium hydroxide, potassium hydroxide, ammonia, sodium acetate, sodium carbonate, sodium bicarbonate, and potassium carbonate.
[0088] [Composition] The present invention also includes compositions comprising the acetal compound of the present invention (hereinafter also referred to as "acetal compound (A)") and at least one component selected from the group consisting of resins other than the acetal compound (A) (B), plasticizers, antioxidants, and ultraviolet absorbers, wherein the content of the acetal compound (A) is 70% by mass or more.
[0089] The composition of the present invention contains 70% by mass or more of the acetal compound (A) of the present invention, and can form a resin sheet that has excellent transparency and puncture resistance, as well as excellent self-supporting and creep resistance in high-temperature environments. The content of acetal compound (A) in the composition of the present invention may be preferably 75% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more. When the content of acetal compound (A) is above the lower limit, transparency, as well as self-supporting and creep resistance in high-temperature environments, tends to improve. The upper limit is not particularly limited and may be, for example, 100% by mass or less.
[0090] The composition of the present invention comprises, in addition to an acetalized compound (A), at least one component selected from the group consisting of a resin other than the acetalized compound (B), a plasticizer, an antioxidant, and an ultraviolet absorber.
[0091] The resin (B) other than the acetalized product (A) that may be included in the composition of the present invention is not particularly limited and includes, for example, polyolefin resins such as polyethylene, polypropylene, polybutene-1, poly-4-methylpentene-1, and polynorbornene; ethylene-based ionomers; styrene-based resins such as polystyrene, styrene-maleic anhydride copolymer, high-impact polystyrene, AS resin, ABS resin, AES resin, AAS resin, ACS resin, and MBS resin; methyl methacrylate polymers and methyl methacrylate-styrene copolymers; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; nylon 6, nylon 66, and Examples include polyamides such as riamide elastomers; polycarbonate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyacetal, polyvinylidene fluoride, polyurethane, modified polyphenylene ether, polyphenylene sulfide, silicone-modified resins, acrylic rubber, acrylic thermoplastic elastomers, silicone rubber; styrene-based thermoplastic elastomers such as SEPS, SEBS, and SIS; olefin-based rubbers such as IR, EPR, and EPDM; ethylene vinyl alcohol copolymers and acetalized ethylene vinyl alcohol copolymers other than acetalized product (A) (hereinafter also referred to as "acetalized product (B)"). These resins may be used individually or in combination of two or more types. As for acetal compound (B), if acetal compound (A) satisfies formulas (1) and (2), for example, the following formula (3): Tm / Tg < 1.27 (3) [In equation (3), Tm and Tg represent the melting peak temperature (Kelvin) and the midpoint glass transition temperature (Kelvin), respectively, measured in accordance with JIS K7121:2012.] Examples include acetalized ethylene vinyl alcohol copolymers that satisfy the above conditions. Furthermore, if the acetalized compound (A) satisfies formula (1) and the meso / racemo ratio of the acetal ring structure is less than 5, then examples include acetalized ethylene vinyl alcohol copolymers with a meso / racemo ratio of 5 or more of the acetal ring structure.
[0092] Among these resins, ethylene vinyl alcohol copolymer and acetal (B) are preferred as resins (B) other than acetal (A) from the viewpoint of easily improving transparency, and acetal (B) is more preferred.
[0093] Examples of the ethylene vinyl alcohol copolymer include the ethylene vinyl alcohol copolymer described in the section on "Method for producing acetalized ethylene vinyl alcohol copolymers" as a raw material for the acetalized acetal of the present invention. However, the ethylene vinyl alcohol copolymer as resin (B) may or may not be porous.
[0094] The acetalized product (B) is not particularly limited as long as it is an acetalized product of an ethylene vinyl alcohol copolymer other than acetalized product (A), for example, an acetalized product of an ethylene vinyl alcohol copolymer that satisfies formula (3) and / or has a meso / racemo ratio of acetal ring structure of 5 or more, and may be a resin containing ethylene units, vinyl alcohol units, acetal units, and optionally vinyl ester units. The content of each unit of the acetalized product (B), degree of acetalization, melting peak temperature Tms, MFR and ΔH AH / ΔH A This may be the same as that described in the section on [acetalized ethylene vinyl alcohol copolymers].
[0095] In one embodiment of the present invention, the Tm / Tg(K / K) of the acetalized product (B) is preferably less than 1.27, more preferably 1.25 or less, even more preferably 1.23 or less, and particularly preferably 1.21 or less, from the viewpoint of easily improving transparency, and from the viewpoint of easily improving self-supporting properties and creep resistance in high-temperature environments, it is preferably 1.10 or more, more preferably 1.12 or more, and even more preferably 1.15 or more. The Tm / Tg(K / K) can be determined by the same method as for the acetalized product (A).
[0096] The content of resin (B) is preferably 25 parts by mass or less per 100 parts by mass of acetal (A), from the viewpoint of easily improving the self-supporting and creep-resistant properties of the resulting resin sheet in a high-temperature environment. Furthermore, from the viewpoint of increasing the fluidity of the composition and easily improving moldability, it may be, for example, 0 parts by mass or more, preferably 5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, and particularly preferably 20 parts by mass or more, per 100 parts by mass of acetal (A).
[0097] Examples of plasticizers that may be included in the composition of the present invention include triethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-2-ethylhexanoate, di-(2-butoxyethyl)-adipate (DBEA), di-(2-butoxyethyl)-sebacate (DBES), di-(2-butoxyethyl)-azelaic acid, di-(2-butoxyethyl)-glutaric acid, di-(2-butoxyethoxyethyl)-adipate (DBEEA), di-(2-butoxyethoxyethyl)-sebacate (DBEES), di-(2-butoxyethoxyethyl)-azelaic acid, di-(2-butoxyethoxyethyl)-glutaric acid, di-(2-hexoxyethyl)-adipate, Examples include di-(2-hexoxyethyl)-sebacate, di-(2-hexoxyethyl)-azelaic acid, di-(2-hexoxyethyl)-glutaric acid, di-(2-hexoxyethoxyethyl)-adipate, di-(2-hexoxyethoxyethyl)-sebacate, di-(2-hexoxyethoxyethyl)-azelaic acid, di-(2-hexoxyethoxyethyl)-glutaric acid, di-(2-butoxyethyl)-phthalate and / or di-(2-butoxyethoxyethyl)-phthalate, polypropylene glycol (PPG), monopropylene glycol dibenzoate, triethylene glycol di-2-ethylhexoate, glycerin mono-12-hydroxystearate, etc. Among these plasticizers, in one embodiment of the present invention, it is preferable that the plasticizer has a sum of 28 or more carbon atoms and oxygen atoms in its molecule. Examples of such plasticizers include triethylene glycol-di-2-ethylhexanoate, tetraethylene glycol-di-2-ethylhexanoate, di-(2-butoxyethyl)-adipate (DBEA), di-(2-butoxyethoxyethyl)-adipate, di-(2-butoxyethoxyethyl)-sebacate, and polypropylene glycol (PPG: average molecular weight 400). These plasticizers may be used individually or in combination of two or more.
[0098] In one embodiment of the present invention, the SP value of the plasticizer is preferably 9.2 (cal / cm²). 3 ) 1 / 2 More preferably 9.3 (cal / cm 3 ) 1 / 2 More preferably 9.5 (cal / cm²) 3 ) 1 / 2 The above is particularly preferably 10.0 (cal / cm³). 3 ) 1 / 2 The above is true, and preferably 12.0 (cal / cm²). 3 ) 1 / 2 More preferably 11.8 (cal / cm³) 3 ) 1 / 2 More preferably, 11.5 (cal / cm²) 3 ) 1 / 2 The following is particularly preferred: 11.2 (cal / cm²) 3 ) 1 / 2 The following applies: When the SP value is above the lower limit and / or below the upper limit, it is easier to suppress plasticizer bleed-out and to further improve the puncture resistance of the resulting resin sheet. The SP value is calculated according to Fedors' calculation method (RFFedors, Polym.Eng.Sci., 14, 147 (1947)).
[0099] The plasticizer content is preferably 40 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and particularly preferably 15 parts by mass or less, per 100 parts by mass of acetal (A), from the viewpoint of easily improving self-supporting properties and creep resistance in high-temperature environments, as well as water resistance, and easily improving adhesion to substrates such as glass, especially low-temperature adhesion. Furthermore, the plasticizer content may be preferably 0 parts by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, even more preferably 10 parts by mass or more, particularly preferably 15 parts by mass or more, and particularly more preferably 17.5 parts by mass or more, per 100 parts by mass of acetal (A). When the plasticizer content is above the lower limit, and especially 10 parts by mass or more per 100 parts by mass of acetal (A), it is easier to suppress plasticizer bleed-out and to easily improve puncture resistance.
[0100] Examples of antioxidants that may be included in the composition of the present invention include phenolic antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and the like. These antioxidants may be used individually or in combination of two or more.
[0101] Examples of phenolic antioxidants include acrylate compounds such as 2-t-butyl-6-(3-t-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate or 2,4-di-t-amyl-6-(1-(3,5-di-t-amyl-2-hydroxyphenyl)ethyl)phenyl acrylate, 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butyl-4-ethylphenol, octadecyl-3-(3,5-)di-t-butyl-4-hydroxyphenyl)propionate, and 2,2'-methylene-bis( 4-methyl-6-t-butylphenol), 4,4'-butylidene-bis(4-methyl-6-t-butylphenol), 4,4'-butylidene-bis(6-t-butyl-m-cresol), ethylenebis(oxyethylene)bis(3-(5-t-butyl-4-hydroxy-m-tolyl)propionate, 4,4'-thiobis(3-methyl-6-t-butylphenol), bis(3-cyclohexyl-2-hydroxy-5-methylphenyl)methane, 3,9-bis(2-(3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionate (Luoxy)-1,1-dimethylethyl)-2,4,8,10-tetraoxaspiro[5,5]undecane, 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis(methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate)methane, triethylene glycol bis(3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionate), ma or alkyl-substituted phenol compounds such as hexamethylenebis(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 6-(4-hydroxy-3,5-di-t-butylanilino)-2,4-bis-octylthio-1,3,5-triazine, 6-(4-hydroxy-3,5-dimethylanilino)-2,4-bis-octylthio-1,3,5-triazine, 6-(4-hydroxy-3-methyl-5-t-butylanilino)-2,4-bis-octylthio-1,3,5-triazine or 2-octylthio-4,6-bis-(3,Examples include triazine group-containing phenolic compounds such as 5-di-t-butyl-4-oxyanilino)-1,3,5-triazine.
[0102] Examples of phosphorus-based antioxidants include triphenyl phosphite, diphenylisodecyl phosphite, phenyl diisodecyl phosphite, tris(nonylphenyl) phosphite, tris(dinonylphenyl) phosphite, tris(2-t-butyl-4-methylphenyl) phosphite, tris(cyclohexylphenyl) phosphite, 2,2-methylenebis(4,6-di-t-butylphenyl)octyl phosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-(3,5-di-t-butyl-4-hydroxybenzyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. Examples include monophosphite compounds such as 10-decyloxy-9,10-dihydro-9-oxa-10-phosphaphenanthrene, and diphosphite compounds such as 4,4'-butylidene-bis(3-methyl-6-t-butylphenyl-di-tridecyl phosphite), 4,4'-isopropylidene-bis(phenyl-di-alkyl(C12~C15) phosphite), 4,4'-isopropylidene-bis(diphenylmonoalkyl(C12~C15) phosphite), 1,1,3-tris(2-methyl-4-di-tridecyl phosphite-5-t-butylphenyl)butane or tetrakis(2,4-di-t-butylphenyl)-4,4'-biphenylene phosphite. Among these, monophosphite compounds are preferred.
[0103] Examples of sulfur-based antioxidants include dilauryl 3,3'-thiodipropionate, distearyl 3,3'-thiodipropionate, lauryl stearyl 3,3'-thiodipropionate, pentaerythritol-tetrakis-(β-lauryl-thiopropionate), and 3,9-bis(2-dodecylthioethyl)-2,4,8,10-tetraoxaspiro[5,5]undecane.
[0104] Among these, preferred antioxidants are phenolic antioxidants, and more preferably alkyl-substituted phenolic antioxidants.
[0105] The antioxidant content is preferably 0 to 5 parts by mass, more preferably 0.001 to 5 parts by mass, and even more preferably 0.01 to 1 part by mass, per 100 parts by mass of acetal (A).
[0106] Examples of UV absorbers that may be included in the composition of the present invention include 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α'dimethylbenzyl)phenyl]-2H-benzotriazole, 2-(3,5-di-t-butyl-2-hydroxyphenyl)benzotriazole, 2-(3-t-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole, and 2-(3,5-di-t-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzo Examples include benzotriazole-based UV absorbers such as riazole, 2-(3,5-di-t-amyl-2-hydroxyphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, or 2-(2-hydroxy-5-t-octylphenyl)benzotriazole, and benzoate-based UV absorbers such as 2,4-di-t-butylphenyl-3,5-di-t-butyl-4-hydroxybenzoate or hexadecyl-3,5-di-t-butyl-4-hydroxybenzoate.
[0107] The amount of ultraviolet absorber may be preferably 0 to 50,000 ppm, more preferably 10 to 50,000 ppm, and even more preferably 100 to 10,000 ppm, on a mass basis relative to the acetal compound (A).
[0108] The composition of the present invention may optionally further contain additives other than those listed above. Examples of additives other than those listed above that may be optionally included include light stabilizers, adhesion modifiers, adhesion improvers, blocking inhibitors, pigments, dyes, and functional inorganic compounds. Among these additives, light stabilizers, adhesion modifiers, and adhesion improvers are preferred. These additives may be used individually or in combination of two or more types.
[0109] Examples of light stabilizers include hindered amine compounds such as 2,2,6,6-tetramethyl-4-piperidyl benzoate, bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)-2-(3,5-di-t-butyl-4-hydroxybenzyl)-2-n-butylmalonate, 4-(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxy)-1-(2-(3-(3,5-di-t-butyl-4-hydroxyphenyl)propionyloxy)ethyl)-2,2,6,6-tetramethylpiperidine, or bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidine) sebacate.
[0110] Adhesion modifiers are additives that reduce adhesive strength. Examples of adhesion modifiers include those disclosed in International Publication No. 03 / 033583, preferably alkali metal salts and / or alkaline earth metal salts of organic acids. More preferably, they are potassium salts, magnesium salts, or calcium salts of carboxylic acids having 1 to 16 carbon atoms, such as potassium acetate, magnesium acetate, magnesium propionate, magnesium butyrate, magnesium 2-ethylbutyrate, magnesium 2-ethylhexanoate, magnesium octoate, magnesium decanoate, magnesium neodecanoate, or calcium stearate.
[0111] Examples of adhesion enhancers include silane coupling agents. Examples of silane coupling agents include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropyldiethoxysilane. These silane coupling agents may be used individually or in combination of two or more.
[0112] If the composition of the present invention contains an adhesion modifier or adhesion improver, the amount thereof may be appropriately selected depending on the type of adhesion improver and the environment in which the laminated glass is used when the resin composition is used as an interlayer raw material for laminated glass. For example, the amount of adhesion improver is preferably adjusted so that the adhesion strength of the resulting resin sheet to glass is generally 3 to 10 in the Pummel test (described in International Publication No. 03 / 033583, etc.), and is preferably adjusted to 3 to 6 when high penetration resistance is required, and to 7 to 10 when high glass shatter resistance is required. When high glass shatter resistance is required, it is also a useful method not to add an adhesion improver.
[0113] If the composition of the present invention contains an adhesion improver, its content may be preferably 0.001 to 5 parts by mass, more preferably 0.01 to 1 part by mass, per 100 parts by mass of acetal (A).
[0114] The content of each additive can be appropriately selected within a range that does not impair the effects of the present invention, and the total content of each additive may be preferably 7% by mass or less, more preferably 5% by mass or less, and even more preferably 4% by mass or less, based on the total mass of the composition.
[0115] In one embodiment of the present invention, the melting peak temperature Tms of the composition of the present invention, measured in accordance with JIS K7121:2012, is preferably 120 to 180°C, more preferably 120 to 175°C, even more preferably 120 to 170°C, even more preferably 125 to 150°C, even more preferably 128 to 145°C, and particularly preferably 130 to 140°C. When the melting peak temperature Tms of the composition is within the above range, transparency is easily improved. In another embodiment of the present invention, the melting peak temperature Tms may be 140 to 170°C, preferably 145 to 165°C, and even more preferably 150 to 160°C. When the melting peak temperature Tms of the composition is within the above range, self-supporting and creep resistance in high-temperature environments are easily improved.
[0116] In one embodiment of the present invention, the melt flow rate (MFR) of the composition of the present invention, measured in accordance with JIS K7210-1:2014 under conditions of 190°C and 2.16 kg, may preferably be 1 to 30 g / 10 min, more preferably 2 to 20 g / 10 min, and even more preferably 3 to 10 g / 10 min, from the viewpoint of easily suppressing thermal degradation during molding.
[0117] In one embodiment of the present invention, the composition of the present invention is, from the viewpoint of easily improving transparency and film-forming properties, the following formula (4): ΔH AH / ΔH A ≤0.30 (4) [In formula (4), ΔH A This represents the heat of fusion of crystals measured using a differential scanning calorimeter (DSC) when the temperature is raised from 25°C to 140°C at a heating rate of 10°C / min, held at 140°C for 30 minutes, then cooled from 140°C to -30°C at a cooling rate of 4°C / min, and then raised again from -30°C to 200°C at a heating rate of 10°C / min, and ΔH AH ΔH A [This shows the heat of fusion on the high-temperature side when the peak is split at 145°C.] It is preferable that the following conditions be met.
[0118] ΔH in the equation AH / ΔH A This represents the ratio of the high-melting-point component to the total crystalline component in the composition, and the high-melting-point component includes EVOH and / or EVOH acetalized products with a low degree of acetalization. In one embodiment of the present invention, the ΔH AH / ΔH A From the viewpoint of easily improving transparency and film-forming properties, the ΔH is preferably 0.30 or less, more preferably 0.25 or less, and even more preferably 0.20 or less. Furthermore, from the viewpoint of easily improving self-supporting properties and creep resistance in high-temperature environments, it is preferably 0.01 or more, more preferably 0.02 or more, and even more preferably 0.03 or more. AH / ΔH A This can be determined using a differential scanning calorimetry (DSC), for example, by the method described in the examples.
[0119] Furthermore, in another embodiment of the present invention, from the viewpoint of easily improving self-supporting and creep resistance in high-temperature environments, the composition of the present invention is defined by the following formula (5): 0.30 < ΔH AH / ΔH A (5) [In the formula, ΔH AH and ΔH A ΔH in equation (4) AH and ΔH A It is the same as] A composition satisfying the following conditions may also be used. In another embodiment of the present invention, from the viewpoint of easily improving self-supporting and creep resistance in high-temperature environments, ΔH AH / ΔH A The value may exceed 0.30, preferably 0.305 or higher, and more preferably 0.31 or higher. Furthermore, from the viewpoint of easily improving transparency and film-forming properties, it may preferably be 0.60 or lower, more preferably 0.50 or lower, and even more preferably 0.40 or lower.
[0120] In a preferred embodiment of the present invention, the resin sheet obtained from the composition of the present invention exhibits values similar to those of the resin sheet of the present invention described in the section on "Resin Sheets" below, including haze, slow-cooling haze, storage modulus, relaxation modulus, and penetration energy. Therefore, the composition of the present invention can form a resin sheet with excellent transparency, penetration resistance, and superior self-supporting and creep resistance in high-temperature environments.
[0121] The uses of the acetal compounds and compositions of the present invention are not particularly limited and can be used in various fields, for example, as packaging materials. Such packaging materials can be used, for example, as containers with excellent oxygen barrier properties in the form of bags, tubes, cups, pouches, etc., for use in food, cosmetics, medical chemicals, toiletries, vacuum insulation boards, etc., or as gas barrier films for food packaging, gasoline tanks, vacuum insulation boards, heat pipes, etc. Furthermore, the acetal compounds and compositions of the present invention are also useful in paper processing agents such as fiber sizing agents, fiber treatment agents, fiber processing agents, sizing agents for textile products, clear coating agents for paper, pigment coating agents for paper, internal sizing agents for paper, binders for thermal paper overcoats, pressure-sensitive adhesives, anti-fogging agents, paints, dispersants for organic and inorganic pigments, polymerization dispersion stabilizers for emulsions, polymerization dispersion stabilizers for PVC, adhesives for paper, wood and plastics, binders for nonwoven fabrics, binders for fibers, binders for ceramics, binders for electrodes, binders for various building materials such as gypsum boards and fiberboards, additives for cement and mortar, hot melt adhesives, resins for 3D printers, adhesives for display films, interlayer adhesives for ceramic laminates, adhesive compositions such as liquid glue and solid glue, separators for storage batteries, laminates with fluororesins, laminates with rubber such as tire inner liners, and composite laminates with fiber substrates. Furthermore, because the acetal compounds and compositions of the present invention have high transparency, they are useful as interlayers for laminated glass, films for agricultural greenhouses, laminates with transparent resins such as resin glazing for vehicles, laminates with antenna circuit boards, protective films for glass surfaces, and various transparent containers for cosmetic applications.
[0122] [Resin sheet] The present invention also includes resin sheets comprising one or more layers (hereinafter also referred to as layer (x)) containing the acetalized EVOH or the composition of the present invention. The resin sheet of the present invention may consist only of layer (x), or it may be a laminate comprising at least one layer (x). The laminate is not particularly limited, but examples include a laminate comprising two or more layers (x), a laminate comprising one or more layers (x) and one or more other layers, etc. When layer (x) or other layers are multiple layers, the resin or resin composition constituting each layer may be the same or different.
[0123] Examples of the aforementioned other layers include layers containing known resins. Examples of such resins include polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyurethane, polytetrafluoroethylene, acrylic resin, polyamide, polyacetal, polycarbonate, and among polyesters, polyethylene terephthalate, polybutylene terephthalate, cyclic polyolefin, polyphenylene sulfide, polytetrachloroethylene, polysulfone, polyethersulfone, polyarylate, liquid crystal polymer, polyimide, thermoplastic elastomer, etc. The other layers may also contain, as needed, one or more additives such as plasticizers, antioxidants, and ultraviolet absorbers, and heat-shielding materials (for example, inorganic heat-shielding fine particles or organic heat-shielding materials having infrared absorption capabilities).
[0124] In one embodiment of the present invention, from the viewpoint of preventing adhesion between resin sheets and improving degassing performance in the lamination process, the resin sheet of the present invention is preferably one having an uneven surface structure. Methods for providing the uneven surface structure include conventionally known methods, such as a method of providing a melt fracture structure by adjusting the extrusion conditions, or a method of imparting an embossed structure to the extruded sheet. The depth and shape of the embossing can be those of conventionally known methods.
[0125] The thickness of one layer (x) in the resin sheet is preferably 0.1 mm or more, more preferably 0.4 mm or more, even more preferably 0.7 mm or more, and also preferably 3 mm or less, more preferably 2.5 mm or less, even more preferably 2 mm or less, even more preferably 1.5 mm or less, and particularly preferably 1 mm or less. If the layer (x) in the resin sheet consists of multiple layers, the thickness of each of the multiple layers (x) in the resin sheet may be the same or different.
[0126] The thickness of the resin sheet is preferably 0.1 mm or more, more preferably 0.4 mm or more, and even more preferably 0.7 mm or more, from the viewpoint of easily improving penetration resistance, and from the viewpoint of ease of handling, it is preferably 3 mm or less, more preferably 2.5 mm or less, even more preferably 2 mm or less, even more preferably 1.5 mm or less, and particularly preferably 1 mm or less.
[0127] The thickness of layer (x)1 in a resin sheet and the thickness of the resin sheet are measured using conventionally known methods, such as contact or non-contact thickness gauges.
[0128] The resin sheet of the present invention has excellent transparency. The haze of the resin sheet of the present invention is preferably 5% or less, more preferably 3% or less, even more preferably 2% or less, and particularly preferably 1% or less. Since the transparency of the resin sheet increases as the haze decreases, the lower limit is not particularly limited and may be, for example, 0.01% or more. The haze of laminated glass is measured using a haze meter in accordance with JIS K7136:2000.
[0129] The resin sheet of the present invention also exhibits excellent transparency (transparency during slow cooling) after heating to 140°C and then slowly cooling from 140°C to 23°C at a rate of 0.1°C / min. Transparency during slow cooling can be evaluated by the haze during slow cooling (slow cooling haze). The slow cooling haze of the resin sheet of the present invention is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and particularly preferably 1% or less. Since the transparency of the resin sheet increases as the haze decreases, the lower limit is not particularly limited and may be, for example, 0.01% or more. The slow cooling haze of the resin sheet can be determined by preparing a laminated glass having the resin sheet as an interlayer, heating the laminated glass to 140°C, and then slowly cooling from 140°C to 23°C at a rate of 0.1°C / min, and measuring the haze with a haze meter in accordance with JIS K7136:2000, for example, by the method described in the examples.
[0130] In one embodiment of the present invention, the storage modulus (E') of the resin sheet of the present invention, measured by dynamic viscoelasticity measurement at 50°C and a frequency of 1 Hz, is preferably 20 MPa or more, more preferably 30 MPa or more, even more preferably 60 MPa or more, and even more preferably 100 MPa or more, from the viewpoint of easily improving self-supporting properties. Furthermore, from the viewpoint of easily improving puncture resistance, it may be preferably 1500 MPa or less, more preferably 1200 MPa or less, and even more preferably 900 MPa or less.
[0131] The resin sheet of the present invention exhibits excellent self-supporting properties in high-temperature environments. Self-supporting properties in high-temperature environments can be evaluated by the storage modulus (E') at 80°C and a frequency of 1 Hz. In one embodiment of the present invention, the storage modulus of the resin sheet of the present invention at 80°C and a frequency of 1 Hz is preferably 5 MPa or higher, more preferably 7 MPa or higher, and even more preferably 10 MPa or higher. The upper limit of the storage modulus is not particularly limited and may be 50 MPa or lower.
[0132] The storage modulus at 50°C and 80°C can be measured, for example, by the method described in the examples, using a dynamic viscoelasticity measuring device.
[0133] The resin sheet of the present invention exhibits excellent creep resistance in high-temperature environments, thus maintaining high strength even after prolonged use. Therefore, when the resin sheet of the present invention is used as an interlayer for laminated glass, its strength does not easily decrease even after prolonged use, making it easier to ensure safety. The creep resistance in high-temperature environments is measured by the relaxation modulus of elasticity after prolonged use (long-term relaxation modulus), for example, 3.2 × 10⁻¹⁰ when a master curve is created at 50°C. 8 It can be evaluated by the relaxation modulus of elasticity after seconds (approximately 10 years). In one embodiment of the present invention, when the master curve was created at 50°C, the result was 3.2 × 10 8 The relaxation modulus after 2 seconds (approximately 10 years) is preferably 0.50 MPa or higher, more preferably 0.60 MPa or higher, even more preferably 0.7 MPa or higher, particularly preferably 0.8 MPa or higher, and most preferably 1.0 MPa or higher. If the relaxation modulus is above the lower limit of the above, the resin sheet and the laminated glass having the resin sheet as an interlayer can exhibit excellent strength even after a long period of time. The upper limit of the relaxation modulus may usually be 5.0 MPa or lower, preferably 4.0 MPa or lower, more preferably 3.5 MPa or lower, even more preferably 3.0 MPa or lower, and particularly preferably 2.0 MPa or lower, from the viewpoint of the handling of the resin sheet. The above relaxation modulus can be determined from a composite curve (referred to as a master curve) at a reference temperature of 50°C, obtained from dynamic viscoelasticity measurement and the time-temperature conversion rule, using a dynamic viscoelasticity measuring device after the resin sheet has been left standing for one week or more in a 23°C, 50% RH atmosphere. For example, it can be determined by the method described in the examples.
[0134] In another embodiment of the present invention, the resin sheet of the present invention, when a master curve is created at 80°C, is 2.6 × 10 6 The relaxation modulus after 2 seconds (approximately 1 month) is preferably 0.5 MPa or higher, more preferably 1.0 MPa or higher, even more preferably 1.5 MPa or higher, and particularly preferably 2.0 MPa or higher. The upper limit of the relaxation modulus is not particularly limited, but may be, for example, 20 MPa or lower.
[0135] The resin sheet of the present invention exhibits excellent puncture resistance. The puncture resistance of the resin sheet can be evaluated by the puncture energy. The puncture energy of the resin sheet of the present invention is preferably 10 J or more, more preferably 12 J or more, and even more preferably 14 J or more. There is no particular upper limit to the puncture energy, and for example, it may be 30 J or less. The puncture energy is measured at 200°C and 50 kgf / cm² for a molten kneaded acetal or acetal-containing composition. 2 A sheet, for example, with a thickness of 0.8 mm, obtained by compression molding at a pressure of (50 MPa) for 5 minutes, can be used as a test specimen and measured in accordance with ASTM D3763 using a drop-weight impact tester, for example, by the method described in the examples.
[0136] [Method for manufacturing resin sheets] The method for producing the resin sheet of the present invention is not particularly limited. For example, the acetalized material or composition of the present invention may be formed into a sheet by known methods such as extrusion molding, press molding, blow molding, injection molding, or solution casting. Among known methods, a preferred method involves supplying the acetalized material and, if necessary, additives to an extruder, kneading and melting the mixture, then extruding the resulting molten mixture from a die and taking it up with a take-up machine to form a sheet. The resin temperature during extrusion is preferably 170 to 250°C, more preferably 180 to 240°C, and even more preferably 190 to 220°C. If the resin temperature during extrusion is below the above upper limit, the decomposition of the acetalized material is suppressed, making it difficult to color. If the resin temperature during extrusion is above the above lower limit, the acetalized material melts completely, making it easier to obtain a sheet with a good appearance and to suppress the generation of volatile substances. Furthermore, in order to efficiently remove volatile substances, it is preferable to remove them from the vent port of the extruder by reducing the pressure.
[0137] [Interlayer for laminated glass] The resin sheet of the present invention is suitably used as an interlayer for laminated glass (hereinafter also simply referred to as an interlayer). Therefore, the present invention encompasses an interlayer for laminated glass made from the resin sheet of the present invention. The interlayer for laminated glass of the present invention is suitably used in various applications such as mobile bodies like automobiles, buildings, and solar cells. In one embodiment of the present invention, the interlayer for laminated glass of the present invention is particularly suitable as an interlayer for laminated glass for structural materials because it has excellent transparency, self-supporting properties, and adhesion to substrates such as glass.
[0138] [Laminated glass] The present invention also includes laminated glass having two glass plates and an interlayer for laminated glass of the present invention disposed between the two glass plates. Because the laminated glass of the present invention includes an interlayer for laminated glass made of the resin sheet of the present invention, it has excellent transparency.
[0139] As the glass plate to be laminated with the interlayer, for example, inorganic glass such as float glass, tempered glass, wired glass, and heat-absorbing glass can be used, as well as conventionally known organic glass such as polymethyl methacrylate and polycarbonate. These may be colorless or colored. One type may be used, or two or more types may be used in combination. The thickness of a single glass plate is not particularly limited, but may be, for example, 1 to 10 mm, preferably 2 to 6 mm. The thicknesses of the two glass plates may be the same or different.
[0140] The laminated glass of the present invention can be manufactured by conventionally known methods. Examples include methods using a vacuum laminator, vacuum bags, vacuum rings, or nip rolls. Alternatively, after temporary bonding by the above methods, the glass may be placed in an autoclave for final bonding.
[0141] When using a vacuum laminator, for example, 1 × 10 -6 ~1 × 10 -1Under a reduced pressure of MPa, laminated glass can be produced by laminating a glass plate, an interlayer film, and any layer (such as an adhesive resin layer, etc.) at 60 to 200 °C, particularly 80 to 160 °C. The method using a vacuum bag or a vacuum ring is described, for example, in European Patent No. 1235683, and at a pressure of about 2×10 -2 ~3×10 -2 MPa, laminated glass can be produced by laminating a glass plate, an interlayer film and any layer at 100 to 160 °C.
[0142] As an example of the manufacturing method using nip rolls, a method is cited in which a glass plate, an interlayer film and any layer are laminated, temporarily adhered at a temperature below the flow start temperature of the acetalized product, and then pressure-bonded at a temperature closer to the flow start temperature. Specifically, for example, after heating to 30 to 70 °C with an infrared heater or the like, degassing is performed with a roll, and after further heating to 50 to 120 °C, pressure-bonding is performed with a roll to adhere or temporarily adhere.
[0143] When further pressure-bonding is performed by charging into an autoclave after temporary adhesion, the operating conditions of the autoclave process are appropriately selected according to the thickness and configuration of the laminated glass, but for example, it is preferable to perform treatment at 130 to 145 °C for 1 to 3 hours under a pressure of 1 to 1.5 MPa.
[0144] The laminated glass of the present invention has excellent transparency because it has the resin sheet of the present invention as an interlayer film for laminated glass. The haze of the laminated glass of the present invention is preferably 5% or less, more preferably 3% or less, still more preferably 2% or less, and particularly preferably 1% or less. Since the transparency of the laminated glass increases as the haze decreases, the lower limit is not particularly limited and may be, for example, 0.01%. The haze of the laminated glass is measured in accordance with JIS K7-136:2000 using a haze meter.
[0145] The laminated glass of the present invention also exhibits excellent transparency (transparency during slow cooling) after heating to 140°C and then slowly cooling from 140°C to 23°C at a rate of 0.1°C / min. Transparency during slow cooling can be evaluated by the haze during slow cooling (slow cooling haze). The slow cooling haze of the laminated glass of the present invention is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, even more preferably 2% or less, and particularly preferably 1% or less. Since a smaller haze increases the transparency of the laminated glass, the lower limit is not particularly limited and may be, for example, 0.01% or more. The slow cooling haze is determined by measuring the haze after heating the laminated glass to 140°C and then slowly cooling from 140°C to 23°C at a rate of 0.1°C / min using a haze meter in accordance with JIS K7136:2000, and can be determined, for example, by the method described in the examples.
[0146] In one embodiment of the present invention, it is preferable that the laminated glass has excellent adhesion between the glass plate and the interlayer. In one embodiment of the present invention, the maximum shear stress measured by the compressive shear strength test described in International Publication No. 1999 / 058334 is preferably 20 MPa or more, more preferably 22 MPa or more, even more preferably 24 MPa or more, and particularly preferably 25 MPa or more. Alternatively, the maximum shear stress may be preferably 40 MPa or less, more preferably 38 MPa or less, and even more preferably 36 MPa or less. If the maximum shear stress is above the lower limit, the adhesion is sufficiently high, which tends to suppress the scattering of glass when the glass breaks, and if it is below the upper limit, it is easier to suppress the decrease in penetration resistance when the glass breaks. The maximum shear stress when the laminated glass delaminates can be used as an indicator of the low-temperature adhesion between the glass and the interlayer of the laminated glass. A higher maximum shear stress indicates higher low-temperature adhesion between the glass and the interlayer.
[0147] The laminated glass of the present invention can be suitably used in automotive windshields, automotive side windows, automotive sunroofs, automotive rear windows, head-up display glass, laminates for facades, exterior walls and roofs, panels, doors, windows, walls, roofs, sunroofs, soundproof walls, display windows, balconies, railing walls and other building materials, partition glass members for conference rooms, solar panels, etc., but is not limited to these uses. [Examples]
[0148] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is as follows: Not limited to this.
[0149] The analytical methods and measurement methods for each physical property of the ethylene vinyl alcohol copolymer (EVOH) used as raw materials in the examples and comparative examples, and the evaluation methods for the resin sheets and laminated glass are shown below.
[0150] <Content and degree of acetalization of each monomer unit> The ethylene vinyl alcohol copolymers used as raw materials in the examples and comparative examples, as well as the acetalized ethylene vinyl alcohol copolymers obtained in the examples and comparative examples, were analyzed for their content (in mol%) of ethylene units, vinyl alcohol units, and acetal units (acetalized vinyl alcohol units) in the ethylene vinyl alcohol copolymers and their acetalized products, as well as their degree of acetalization, as described below.
[0151] Ethylene vinyl alcohol copolymer was dissolved in dimethyl sulfoxide (DMSO) at 120°C, and the resulting DMSO solution was cooled to room temperature. Then, N,N-dimethyl-4-aminopyridine and acetic anhydride were added to the DMSO solution and stirred for 1 hour to allow the reaction to proceed. The copolymer was reprecipitated from the resulting reaction solution using deionized water and acetone, washed, and then dried to obtain ethylene vinyl acetate copolymer. The deuterated dimethyl sulfoxide (DMSO-d6) solution of the obtained ethylene vinyl acetate copolymer was measured using a 400 MHz proton NMR spectrometer with 256 cumulative measurements. From the resulting spectrum, the ethylene unit content (n) relative to the total monomer units constituting the ethylene vinyl alcohol copolymer was calculated from the intensity ratio of the methine proton peaks (1.1-1.9 ppm peaks) derived from ethylene units and vinyl acetate units, and the terminal methyl proton peak (2.0 ppm peak) derived from vinyl acetate units. Since ethylene units are not affected by the acetalization reaction, the ethylene unit content (n) in an ethylene vinyl alcohol copolymer is equal to the ethylene unit content (n) relative to the total monomer units constituting the acetalized EVOH obtained after acetalization of the ethylene vinyl alcohol copolymer. The content of vinyl alcohol units (l), vinyl acetate units (m), and acetal units (k) relative to the total monomer units constituting the acetalized EVOH was determined by the following method. A DMSO-d6 solution of the acetalized EVOH was measured using a 400 MHz proton NMR spectrometer with 256 cumulative measurements. From the obtained spectrum, the content of each monomer unit was calculated using the intensity ratio of the methine proton peaks (peaks from 1.0 to 1.8 ppm) derived from ethylene units, vinyl alcohol units, and vinyl acetate units, and the terminal methyl proton peaks (peaks from 0.8 to 1.0 ppm) derived from acetal units, as well as the ethylene unit content (n) of the ethylene vinyl alcohol copolymer.
[0152] The degree of acetalization of the acetalized EVOH was determined using the following formula, based on the content of vinyl alcohol units (l), vinyl acetate units (m), and acetal units (k) obtained above. Acetalization degree (mol %) = {k / (k+l+m)} × 100
[0153] <Symmetry coefficient (W 0.05h / 2f)> The symmetry coefficients of the acetal compounds obtained in the examples and comparative examples were determined by reverse-phase partition gradient high-performance liquid chromatography (HPLC) analysis using a water-ethanol eluent under the following conditions, in accordance with JIS K 0124:2011. The "W" in the symmetry coefficients is... 0.05h " represents the peak width at 1 / 20th of the peak height from the baseline (5% peak height position) of the measured peak obtained by HPLC analysis, and "f" represents the distance on the rising side of the peak when the peak width at 5% peak height position is divided by a perpendicular line containing the peak apex. (Measurement conditions for HPLC analysis) Sample concentration: 1.5 mg / 1 g Sample solvent: EtOH (99.5%) / ion-exchanged water = 9 / 1 wt% mixed solvent Injection volume: 20μL Detector: Varian 380-LC, EVAP 80°C (pre-stage heating), NEB 50°C (second stage heating), Gas 1.5 (SLM), data acquisition interval 1000 msec, filter 1 μm ODS Silica Column: Shimadzu Corporation's "Shimpack G-ODS (Octadecyl group modified spherical fully porous silica gel, inner diameter 4 mm x length 10 mm, particle size 5 μm)" Column temperature: 45℃ Fluid delivery rate: Total flow rate 0.4 mL / min (HPLC analysis procedure) Water was used as mobile phase A and ethanol (99.5%) as mobile phase B. Before sample injection, the column of the HPLC system was filled with a mixed solvent of mobile phase A / mobile phase B in a volume ratio of 95 / 5. The sample was then injected. The solvent was then flowed under the following conditions. 0~5 minutes (B concentration;_5% constant) 5~25 minutes (B concentration;_5~100%) 25~30 minutes (B concentration; 100% constant) 30~31 minutes (B concentration; 100~5%) 31~55 minutes (B concentration;_5% constant)
[0154] <Tm / Tg(K / K)> The acetalized samples obtained in the examples and comparative examples were heated to a differential scanning calorimeter (DSC) (Mettler Toledo, TGA / DSC1 Star System) from 25°C to 230°C at a heating rate of 10°C / min to melt the samples. After cooling from 230°C to -30°C at a heating rate of 10°C / min, the samples were heated again from -30°C to 230°C at a heating rate of 10°C / min. The melting peak temperature Tm (°C) and the midpoint glass transition temperature Tg (°C) were measured in accordance with JIS K7121:2012. The obtained values were converted to Kelvin (K) units, and Tm / Tg (K / K) was calculated.
[0155] <Meso / Rasemo ratio> 13C-NMR measurements were carried out using a Bruker spectrometer model AV600. In a 10 mm diameter NMR tube, the acetalized products obtained in the examples and comparative examples were dissolved in deuterated dimethyl sulfoxide (DMSO) to prepare a 12 wt% acetalized product solution. Chromium(III) acetylacetonate was added in an amount of 0.9 wt% as a relaxant. The NMR measurements were carried out at 80 °C in the gated decoupling mode. From the obtained spectra, the intensity ratio of the peak (peak at 98.0 - 102 ppm) derived from the methine C atom of the acetal moiety of the six-membered butyral ring having a meso form, and the peak (peak at 91.0 - 95.0 ppm) derived from the methine C atom of the acetal moiety of the six-membered butyral ring having a racemo form was used to calculate the meso / racemo ratio.
[0156] <SP value> The SP values of the acetalized products obtained in the examples and comparative examples, and the SP values of the plasticizers used in the examples and comparative examples were calculated according to Fedors' calculation method.
[0157] <tms> The acetalized compositions obtained in the examples and comparative examples were heated to a differential scanning calorimeter (DSC) (Mettler Toledo, TGA / DSC1 Star System) from 25°C to 230°C at a heating rate of 10°C / min to melt the samples. After cooling from 230°C to -30°C at a cooling rate of 10°C / min, the temperature was raised again from -30°C to 230°C at a heating rate of 10°C / min. The melting peak temperature Tms (°C) measured at this temperature was determined in accordance with JIS K7121:2012.
[0158] <Melt Flow Rate (MFR)> The melt flow rate of the ethylene vinyl alcohol copolymers used in the examples and comparative examples was measured in accordance with JIS K7210:2014 under conditions of 190°C and a 2.16 kg load.
[0159] <Median diameter of pores, surface area of pores> After freeze-drying the EVOH porous materials obtained in each of the production examples described below, or the EVOH acetalized materials obtained in the examples and comparative examples at -80°C, 0.5 g was placed in a standard 5 cc powder cell (stem volume 0.4 cc), and the median diameter and surface area of pores with a diameter in the range of 0.005 to 100 μm were measured using a micromeristics pore distribution analyzer (Shimadzu Corporation, Autopore V9620) under an initial pressure of 2.6 kPa. The median diameter of the pores is the median diameter (d50) for all pores with a diameter in the range of 0.005 to 100 μm in the log differential pore volume distribution. The mercury parameters were set to a mercury contact angle of 130 degrees and a mercury surface tension of 485 hynes / cm.
[0160] <Presence or absence of pores at the center of gravity of a porous material> A cross-section of the EVOH porous body perpendicular to the pore orientation direction (extrusion direction) passing through the center of gravity of the EVOH porous bodies obtained in Production Examples 1 to 5 described below was prepared with a single-edge razor while being frozen with liquid nitrogen. The prepared cross-section of the porous body was observed with a scanning electron microscope (SEM, SU-70 manufactured by Hitachi High-Tech Corporation), and it was evaluated whether each porous body had pores in the center of gravity part.
[0161] <Average particle diameter> For 100 g of the ethylene-vinyl alcohol copolymer obtained in Production Examples 1 to 5 described below, the average particle diameter of the measurement sample (lyophilized EVOH porous pellets) was measured using "CAMSIZER XT" of VERDER Scientific. The particle diameter (Q3 50.0%) at which the cumulative particle size distribution from the small particle size side of the equivalent circle particle diameter calculated by the dynamic image analysis method conforming to ISO 13322-2 (2006) was 50% (volume basis) was defined as the average particle diameter.
[0162] <ΔH AH / ΔH A > The melt-kneaded products of the acetalized products and compositions obtained in the examples and comparative examples were heated from 25°C to 140°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC) (TGA / DSC1 Star System manufactured by Mettler Toledo), then held at 140°C for 30 minutes, cooled from 140°C to -30°C at a cooling rate of 4°C / min, and the heat of crystal melting (ΔH A ) measured when heating from -30°C to 200°C again at a heating rate of 10°C / min. The obtained ΔH A was peak-split at 145°C, and the heat of crystal melting on the high-temperature side was defined as ΔH AH , and ΔH AH / ΔH A was calculated. The measurement results obtained in Example 1 are shown in Figure 2.
[0163] <Transparency> (Haze of resin sheet) Test specimens measuring 20 mm in length and 5 mm in width were cut from the resin sheets obtained in the examples and comparative examples. The haze of the obtained test specimens was measured using a haze meter (SH7000, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7136:2000. (Haze during slow cooling of laminated glass (slow cooling haze)) The laminated glass obtained in the examples and comparative examples was cut to a size of 25 mm x 25 mm to obtain test samples. The obtained test samples were heated to 140°C and then slowly cooled to 23°C at a rate of 0.1°C / min. The haze of the test samples after the slow cooling operation was measured using a haze meter (SH7000, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K7136:2000.
[0164] <Self-supporting properties under high-temperature conditions (storage modulus at 80°C)> The self-supporting properties of the resin sheets obtained in the examples and comparative examples under high-temperature environments were evaluated by measuring the storage modulus at 80°C. Test specimens measuring 20 mm in length and 5 mm in width were cut from the resin sheets obtained in the examples and comparative examples, and the storage modulus (E') was measured using a dynamic viscoelasticity analyzer (manufactured by UBM Co., Ltd.) under the conditions of a measurement temperature of 80°C and a frequency of 1 Hz.
[0165] <Creep resistance (long-term relaxation modulus)> The resin sheets obtained in the examples and comparative examples were left to stand for at least one week at 23°C in a 50%RH atmosphere. Then, test pieces measuring 40 mm in length and 5 mm in width were cut out, and the long-term relaxation modulus was determined from the composite curve (master curve) obtained from dynamic viscoelasticity measurement and the time-temperature conversion rule using a dynamic viscoelasticity measuring device manufactured by UBM Co., Ltd., with a reference temperature of 50°C. This value was used as an indicator of the strength of the resin sheet after a long period of time. A higher long-term relaxation modulus indicates higher strength of the resin sheet after a long period of time. Dynamic viscoelasticity measurements were performed according to the method compliant with JIS K 0129:2005, with tensile measurements conducted under conditions of temperature 50-100°C and frequencies of 0.1, 0.5, 1, 5, 10, 50, and 100 Hz. From the obtained storage modulus measurement results, a master curve was created using the temperature-time conversion rule, with the reference temperature set to 50°C, and the frequency was set to 3.2 × 10⁻⁶. -9 Storage modulus (E'(t1)) at Hz, and frequency 1.6 × 10 -9 The loss modulus of elasticity (E''(t2)) at Hz is read, Poisson's ratio is fixed at 0.5, and the following formula (A) is used: 50℃, 3.2 × 10 8 The relaxation modulus G(t) after seconds was calculated. G(t)=E'(t1) / 3-0.4×E''(t2) / 3...(A) These calculations were performed using "RheoStation" (UBM Corporation), the calculation software included with the dynamic viscoelasticity measuring device manufactured by UBM Corporation. Similarly, tensile measurements were performed under conditions of temperature 80-140°C and frequencies of 0.1, 0.5, 1, 5, 10, 50, and 100 Hz, according to the method compliant with JIS K 0129:2005. From the obtained storage modulus measurement results, a master curve was created using the temperature-time conversion rule with a reference temperature of 80°C, and the frequency was set to 4.0 × 10⁻⁶. -7 Storage modulus (E'(t1)) at Hz, and frequency 2.0 × 10 -7 By reading the loss modulus (E''(t2)) at Hz and fixing Poisson's ratio to 0.5, we obtain 2.6 × 10 at 80°C using equation (A). 6 The relaxation modulus after [number] seconds was calculated.
[0166] <Penetration resistance> The acetalized compounds and compositions obtained in the examples and comparative examples were heated at 200°C at a rate of 50 kgf / cm². 2 A 0.8 mm thick resin sheet was obtained by compression molding at a pressure of 5 minutes. A 60 mm x 60 mm test piece was cut from the resin sheet, and a drop-weight impact test was performed using an Instron "CEAST9350" machine in accordance with ASTM D3763-18, under the conditions of a measurement temperature of 23°C, a load of 2 kg, and an impact velocity of 9 m / sec. The penetration energy was calculated from the area of the SS curve from the moment the striker tip touched the test piece (sensing the test force) to the moment of penetration (when the test force returned to zero).
[0167] <Ball Drop Test> The edges of the laminated glass obtained in the examples and comparative examples were fixed to a support frame and held horizontally. A 2.26 kg steel ball was then dropped from a height of 1.5 m onto the center of the laminated glass test piece. Ten repeated tests were performed and evaluated according to the following criteria. A result of A or B in the ball drop test indicates that the laminated glass has superior penetration resistance. This test was conducted while maintaining the temperature of the laminated glass at 20°C. (Evaluation criteria for the ball drop test) A: I was able to prevent the steel ball from penetrating me more than five times. B: The number of times the steel ball was prevented from penetrating was less than 5, and 2 or more. C: The steel ball was prevented from penetrating less than twice.
[0168] <Film forming properties> The acetalized compounds and compositions obtained by the method described later were used to produce resin sheets with a thickness of 0.8 mm and a width of 50 cm using a 40 mm diameter full-flight single-screw extruder and a 60 cm wide coat hanger die at a barrel temperature of 200 °C. The film formation stability was observed and evaluated according to the following criteria, which were used as indicators of film formation performance. (Evaluation criteria for film-forming properties) A: Continuous film formation was possible without any problems, and a resin sheet with a good appearance was obtained. B: Although some problems such as tearing and loosening occurred at the edges of the resin sheet, continuous film formation was possible, and a resin sheet with a relatively good appearance was obtained. C: Problems such as breakage and loosening of the resin sheet occurred, making continuous film formation impossible, and resulting in the inability to obtain a resin sheet with a good appearance.
[0169] <Low-temperature adhesion (maximum shear stress)> The maximum shear stress of the laminated glass obtained in the examples and comparative examples was measured according to the method described as a compressive shear strength test in International Publication No. 1999 / 058334. The obtained maximum shear stress was used as an evaluation index for the low-temperature adhesion between the glass and the resin sheet. The evaluation criteria are shown below. A: Maximum shear stress is 25 MPa or higher B: Maximum shear stress is between 20 MPa and 25 MPa C: Maximum shear stress is less than 20 MPa
[0170] In the examples and comparative examples, pelletized ethylene vinyl alcohol copolymers (EVOH1 to EVOH5) produced by the following methods were used as raw materials.
[0171] <Manufacturing Example 1> An EVOH solution containing 100 parts by mass of EVOH with an ethylene unit content of 44 mol% and a degree of saponification of 99.98 mol%, 60 parts by mass of methanol, and 40 parts by mass of water was continuously supplied from the top stage of a 0.3 m diameter, 10-stage tray column, and steam was blown in from the bottom stage, bringing the EVOH solution and steam into contact in a countercurrent. The temperature inside the column was 130°C and the pressure inside the column was 0.3 MPa. The hydrated EVOH obtained by contacting it with steam in a countercurrent was withdrawn from the bottom of the column. The temperature of the obtained hydrated EVOH was 120°C and the water content was 52.4% by mass. The methanol content was 0.02% by mass. Water-containing EVOH was supplied at 42 kg / hr to a twin-screw extruder with a back slit, and extruded under the following conditions through a die with 8 holes and a hole diameter of 3.0 mm, attached to the tip of the extruder. The extruded molten material was cut with a hot cutter having two blades at a distance of 0.05 mm from the die to obtain a flattened spherical pellet-shaped porous EVOH body. The flow rate of the cutter circulating water was 300 liters / min, and the rotation speed of the cutter blades was 3000 rpm. At this time, the resin temperature (outlet) was 95°C, and the moisture content was 34% by mass. <Conditions for a twin-screw extruder> L / D: 14 Caliber: 30mm Screw: Full Flight Rotation speed: 300 rpm Cylinder temperature: 90℃ Die temperature: 120℃ The obtained EVOH porous material was washed with water at 50°C until the sodium acetate content was 0.002% by mass or less (sodium equivalent), and the washing water was filtered off to obtain a flattened spherical pellet-shaped porous material of ethylene vinyl alcohol copolymer (EVOH1). The obtained EVOH1 was a flattened spherical pellet with an average particle diameter of 3.2 mm. The EVOH1 pellets had pores ranging in diameter from 0.003 μm to 100 μm, with a median pore diameter of 0.07 μm. Observation with an electron microscope confirmed that the porous material had pores at its center of gravity, and that in a cross-section of the porous material passing through its center of gravity, when the shortest distance L from the center of gravity of the cross-section to the surface of the porous material was defined as the distance L, the pores were found in a region within 10% of the distance L from the center of gravity of the cross-section. Table 1 shows the median pore diameter, average particle diameter, and pore surface area of the obtained EVOH1.
[0172] <Manufacturing Example 2> A porous body of ethylene vinyl alcohol copolymer (EVOH2) in pellet form was obtained in the same manner as in Production Example 1, except that the ethylene content was set to 32 mol%. The obtained EVOH2 pellets were flattened and spherical with an average particle diameter of 3.2 mm. The EVOH2 pellets had pores ranging in diameter from 0.003 μm to 100 μm, with a median pore diameter of 0.11 μm. Observation with an electron microscope confirmed that the porous material had pores at its center of gravity and within 10% of the distance L from the center of gravity in the cross-section of the porous material. Table 1 shows the median diameter, average particle size, and pore surface area of the obtained EVOH2 pores.
[0173] <Manufacturing Example 3> The ethylene vinyl alcohol copolymer (EVOH1) obtained in Production Example 1 was fed into a twin-screw extruder and pelletized at a resin temperature of 100°C at the discharge port. The input rate of EVOH1 per unit time was 10 kg / hr. The specifications of the twin-screw extruder are shown below. <Conditions for a twin-screw extruder> L / D: 45.5 Caliber: 30mmΦ Screw: Fully meshing in the same direction Rotation speed: 300 rpm Die diameter: 3.0mmΦ Number of dice holes: 5 The obtained pellets were dried in a fluidized bed dryer at 100°C for 15 hours, and then dried in a static dryer at 100°C for another 15 hours to obtain pelletized ethylene vinyl alcohol copolymer (EVOH3). The obtained EVOH3 pellets were spherical with an average particle diameter of 2.9 mm, and observation with an electron microscope did not confirm that EVOH3 had pores. The average particle diameter and pore surface area of the obtained EVOH3 are shown in Table 1.
[0174] <Manufacturing Example 4> A porous body of ethylene vinyl alcohol copolymer (EVOH4) in pellet form was obtained in the same manner as in Production Example 1, except that the ethylene content was set to 27 mol%. The obtained pellets of EVOH4 were flat spherical with an average particle diameter of 3.2 mm. The pellets of EVOH4 had pores with diameters ranging from 0.003 μm to 100 μm, and the median diameter of the pores was 0.11 μm. As a result of observation with an electron microscope, it was confirmed that the porous body had pores in the center of gravity part and that the porous body had pores in the region within 10% of the distance L from the center of gravity of the cross section of the porous body. The median diameter, average particle diameter, and pore surface area of the obtained pores of EVOH4 are shown in Table 1.
[0175] <Production Example 5> A porous body (EVOH5) of a pellet-shaped ethylene-vinyl alcohol copolymer was obtained in the same manner as in Production Example 1, except that the ethylene content in Production Example 1 was changed to 15 mol%. The obtained pellets of EVOH5 were flat spherical with an average particle diameter of 3.2 mm. The pellets of EVOH5 had pores with diameters ranging from 0.003 μm to 100 μm, and the median diameter of the pores was 0.05 μm. As a result of observation with an electron microscope, it was confirmed that the porous body had pores in the center of gravity part and that the porous body had pores in the region within 10% of the distance L from the center of gravity of the cross section of the porous body. The median diameter, average particle diameter, and pore surface area of the obtained pores of EVOH5 are shown in Table 1.
[0176] <Production Example 6> A porous body (EVOH6) of a pellet-shaped ethylene-vinyl alcohol copolymer was obtained in the same manner as in Production Example 1, except that the ethylene content in Production Example 1 was changed to 38 mol%. The obtained pellets of EVOH6 were flat spherical with an average particle diameter of 3.2 mm. The pellets of EVOH6 had pores with diameters ranging from 0.003 μm to 100 μm, and the median diameter of the pores was 0.08 μm. As a result of observation with an electron microscope, it was confirmed that the porous body had pores in the center of gravity part and that the porous body had pores in the region within 10% of the distance L from the center of gravity of the cross section of the porous body. The pore surface area of the obtained EVOH6 was 33 (m 2 / g).
[0177] <Example 1> (Synthesis of acetalized ethylene vinyl alcohol copolymers) 100 parts by mass of the EVOH porous material (EVOH2) obtained in Production Example 2 was dispersed in 377 parts by mass of water, and 20.0 parts by mass of isobutyraldehyde was added. The resulting dispersion was heated to 60°C under stirring. Stirring was continued for 2 hours to impregnate the ethylene vinyl alcohol copolymer with isobutyraldehyde. Then, at 60°C, 10 parts by mass of 1 M hydrochloric acid was added to the dispersion to carry out the acetalization reaction. Two hours after the first addition of hydrochloric acid, 40 parts by mass of 1 M hydrochloric acid was added, and the acetalization reaction was carried out for a further 4 hours. The acetal product produced by acetalization was in a solid state. Then, the acetalization reaction was stopped by neutralizing the dispersion with 75 parts by mass of 1 M sodium hydroxide. To neutralize the solid interior of the acetal product, the dispersion was stirred at 60°C for a further 8 hours. The neutralized acetalized material was filtered off, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it. The acetalized material was filtered off again, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it a second time. The washing water was filtered off, and vacuum drying was carried out at 60°C for 8 hours to obtain 113 parts by mass (100% yield) of pelletized ethylene vinyl alcohol copolymer acetalized material (A-1). The ethylene unit content of the obtained EVOH acetalized material was 32 mol%, and the degree of acetalization was 29 mol%. Furthermore, the obtained EVOH acetalized material was a porous material having a pore structure similar to that of the raw material EVOH2.
[0178] The acetalized EVOH obtained above was melted and kneaded for 3 minutes at a chamber temperature of 200°C and a rotation speed of 100 rpm using a Laboplast Mill (Toyo Seiki Seisakusho Co., Ltd., "4M150"). The contents of the chamber were removed and cooled to obtain a molten mixture. The resulting molten mixture was heated at 210°C at a rate of 50 kgf / cm². 2 A resin sheet with a thickness of 0.8 mm was obtained by compression molding at a pressure of 50 MPa for 5 minutes. The obtained sheet was sandwiched between two sheets of float glass with a thickness of 2.7 mm, and then put into a vacuum laminator (1522N manufactured by Nisshinbo Mechatronics Co., Ltd.). The inside of the vacuum laminator was depressurized at 100 °C for 1 minute. While maintaining the depressurization and temperature, it was pressed at 30 kPa for 5 minutes to obtain a temporary adhesive. The obtained temporary adhesive was put into an autoclave and treated at 140 °C and 1.2 MPa for 30 minutes to obtain laminated glass.
[0179] <Examples 2 to 4> Except that the type of the ethylene-vinyl alcohol copolymer used and the amount of aldehyde added were changed as shown in Table 1, acetalized products (A-2), (A-3) and (A-4) of the pelletized ethylene-vinyl alcohol copolymer were obtained in the same manner as in Example 1. The obtained acetalized products of the ethylene-vinyl alcohol copolymer were porous bodies having the same pore structure as the raw material ethylene-vinyl alcohol copolymer. Using the obtained acetalized products of the ethylene-vinyl alcohol copolymer, melt-kneaded products, resin sheets and laminated glass were obtained in the same manner as in Example 1.
[0180] <Comparative Example 1> Except that the type of the ethylene-vinyl alcohol copolymer used as a raw material and the amount of aldehyde added were changed as shown in Table 1, an acetalized product (B-2) of EVOH was obtained in the same manner as in Example 1. Using the obtained acetalized product of EVOH, melt-kneaded products, resin sheets and laminated glass were obtained in the same manner as in Example 1.
[0181] <Comparative Example 2> Except that the type of the ethylene-vinyl alcohol copolymer used as a raw material and the amount of aldehyde added were changed as shown in Table 1 and aldehyde impregnation was not performed, an acetalized product (B-3) of EVOH was obtained in the same manner as in Example 1. Using the obtained acetalized product of EVOH, melt-kneaded products, resin sheets and laminated glass were obtained in the same manner as in Example 1.
[0182] <Comparative Example 3> 100 parts by mass of the EVOH porous material (EVOH1) obtained in Production Example 1 was dispersed in a mixed solvent of 500 parts by mass of methanol and 50 parts by mass of ion-exchanged water. Then, 40 parts by mass of 1 M hydrochloric acid was added, and the temperature of the resulting dispersion was raised to 60°C under stirring to completely dissolve the chips. Subsequently, 16.7 parts by mass of isobutyraldehyde was added to the homogeneous solution of ethylene vinyl alcohol copolymer and dispersed, and the acetalization reaction was carried out while maintaining the temperature at 60°C. After holding for 3 hours from the start of the reaction, 6.4 parts by mass of sodium carbonate was added to stop the reaction, and a reaction solution containing modified vinyl acetal resin was obtained.
[0183] After neutralization, 500 parts by mass of methanol were added to the reaction solution, and then 2000 parts by mass of deionized water were added dropwise to precipitate the resin. After filtering the precipitated resin, the resin was dispersed in deionized water, stirred and washed at 23°C for 15 minutes, and then filtered. This washing and filtration process was repeated two more times. This washing process from precipitation to washing and filtration constituted one set. Subsequently, the resin was dissolved in 1000 parts by mass of methanol, and another set of washing was performed. After this, the resin composition was obtained by vacuum drying at 60°C for 8 hours. The modified vinyl acetal resin (B-1) contained in the obtained resin composition had an ethylene unit content of 44 mol% and a degree of acetalization of 30 mol%. Using the obtained acetalized ethylene vinyl alcohol copolymer, a molten compound, a resin sheet, and laminated glass were obtained in the same manner as in Example 1.
[0184] <Comparative Example 4> Except for changing the type of ethylene vinyl alcohol copolymer used as a raw material and the amount of aldehyde added, as shown in Table 1, EVOH acetal (B-4) was obtained in the same manner as in Example 1. Using the obtained EVOH acetal, a molten compound, a resin sheet, and laminated glass were obtained in the same manner as in Example 1.
[0185] <Comparative Example 5> Except for changing the type of ethylene vinyl alcohol copolymer used as a raw material, the amount of aldehyde added, and the reaction time as shown in Table 1, and omitting aldehyde impregnation, EVOH acetal (B-5) was obtained in the same manner as in Example 1. Using the obtained EVOH acetal, a molten compound, a resin sheet, and laminated glass were obtained in the same manner as in Example 1.
[0186] The various physical properties of the acetalized materials, resin sheets, and laminated glass obtained in Examples 1-3 and Comparative Examples 1-5 were evaluated according to the method described above. The results are shown in Table 1.
[0187] [Table 1]
[0188] <Example 5> A composition obtained by mixing 100 parts by mass of an acetalized ethylene vinyl alcohol copolymer (A-1) and 0.02 parts by mass of a phenolic antioxidant (BASF Japan Ltd., "Irganox 1010") was melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet and laminated glass were obtained in the same manner as in Example 1.
[0189] <Examples 6 and 7> Except for changing the acetalized ethylene vinyl alcohol copolymer used as shown in Table 2, a molten kneaded product of the composition, a resin sheet, and laminated glass were obtained in the same manner as in Example 5.
[0190] <Example 8> 80 parts by mass of an acetalized product (A-2) of an ethylene-vinyl alcohol copolymer and 20 parts by mass of an acetalized product (B-1) of an ethylene-vinyl alcohol copolymer were mixed, and the resulting composition was melt-kneaded using a lab plast mill at a chamber temperature of 200 °C and a rotation speed of 100 rpm for 3 minutes. The chamber contents were taken out and cooled to obtain a melt-kneaded product. Using the obtained melt-kneaded product, a resin sheet and laminated glass were obtained in the same manner as in Example 1.
[0191] <Example 9> 100 parts by mass of an acetalized product (A-4) of an ethylene-vinyl alcohol copolymer and 10 parts by mass of di-(2-butoxyethyl)-adipate (DBEA) were melt-kneaded using a lab plast mill at a chamber temperature of 200 °C and a rotation speed of 100 rpm for 3 minutes. The chamber contents were taken out and cooled to obtain a melt-kneaded product. Using the obtained melt-kneaded product, a resin sheet and laminated glass were obtained in the same manner as in Example 1.
[0192] <Example 10> 100 parts by mass of an acetalized product (A-2) of an ethylene-vinyl alcohol copolymer and 22 parts by mass of polypropylene glycol (average molecular weight 400: manufactured by Sanyo Chemical Industries, Ltd., "Sunnix PP-400") were melt-kneaded using a lab plast mill at a chamber temperature of 200 °C and a rotation speed of 100 rpm for 3 minutes. The chamber contents were taken out and cooled to obtain a melt-kneaded product. Using the obtained melt-kneaded product, a resin sheet and laminated glass were obtained in the same manner as in Example 1.
[0193] <Example 11> (Synthesis of Acetalized Product of Ethylene-Vinyl Alcohol Copolymer) 100 parts by mass of the EVOH porous material (EVOH4) obtained in Production Example 4 was dispersed in 377 parts by mass of water, and 9.0 parts by mass of isobutyraldehyde was added. The resulting dispersion was heated to 60°C under stirring. Stirring was continued for 2 hours to impregnate the ethylene vinyl alcohol copolymer with isobutyraldehyde. Then, at 60°C, 10 parts by mass of 1 M hydrochloric acid was added to the dispersion to carry out the acetalization reaction. Two hours after the first addition of hydrochloric acid, 40 parts by mass of 1 M hydrochloric acid was added, and the acetalization reaction was carried out for a further 4 hours. The acetal product produced by acetalization was in a solid state. Then, the acetalization reaction was stopped by neutralizing the dispersion with 75 parts by mass of 1 M sodium hydroxide. To neutralize the solid interior of the acetal product, the dispersion was stirred at 60°C for a further 8 hours. The neutralized acetalized material was filtered off, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it. The acetalized material was filtered off again, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it a second time. The washing water was filtered off, and vacuum drying was carried out at 60°C for 8 hours to obtain 103 parts by mass (100% yield) of pelletized ethylene vinyl alcohol copolymer acetalized material (A-5). The obtained EVOH acetalized material had an ethylene unit content of 27 mol%, a vinyl alcohol unit content of 68.6 mol%, and a degree of acetalization of 12 mol%. Furthermore, the obtained EVOH acetalized material was a porous body having a pore structure similar to that of the raw material EVOH4. The obtained acetal product (A-5) of ethylene vinyl alcohol copolymer had a symmetry coefficient of 0.79, a Tg of 55°C, a Tm of 151°C, and a Tm / Tg(K / K) of 1.29.
[0194] The composition obtained by mixing 100 parts by mass of the acetalized ethylene vinyl alcohol copolymer (A-5) and 0.02 parts by mass of an antioxidant (BASF Japan Ltd., "Irganox 1010") was melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet and laminated glass were obtained in the same manner as in Example 1.
[0195] <Example 12> 100 parts by mass of ethylene vinyl alcohol copolymer acetal (A-5) and 20 parts by mass of polypropylene glycol (average molecular weight 400: Sanyo Chemical Industries, Ltd., "Sannix PP-400") were melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet and laminated glass were obtained in the same manner as in Example 1.
[0196] <Example 13> 100 parts by mass of the EVOH porous material (EVOH4) obtained in Production Example 4 was dispersed in 377 parts by mass of water, and 23.3 parts by mass of isobutyraldehyde was added. The resulting dispersion was heated to 60°C under stirring. Stirring was continued for 2 hours to impregnate the ethylene vinyl alcohol copolymer with isobutyraldehyde. Then, at 60°C, 10 parts by mass of 1 M hydrochloric acid was added to the dispersion to carry out the acetalization reaction. Two hours after the first addition of hydrochloric acid, 40 parts by mass of 1 M hydrochloric acid was added, and the acetalization reaction was carried out for a further 4 hours. The acetal product produced by acetalization was in a solid state. Then, the acetalization reaction was stopped by neutralizing the dispersion with 75 parts by mass of 1 M sodium hydroxide. To neutralize the solid interior of the acetal product, the dispersion was stirred at 60°C for a further 8 hours. The neutralized acetalized material was filtered off, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it. The acetalized material was filtered off again, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it a second time. The washing water was filtered off, and vacuum drying was carried out at 60°C for 8 hours to obtain 117 parts by mass (100% yield) of pelletized ethylene vinyl alcohol copolymer acetalized material (A-6). The obtained EVOH acetalized material had an ethylene unit content of 27 mol%, a vinyl alcohol unit content of 56.9 mol%, and a degree of acetalization of 22 mol%. Furthermore, the obtained EVOH acetalized material was a porous material having a pore structure similar to that of the raw material EVOH4. The acetalized product (A-6) of the obtained ethylene vinyl alcohol copolymer had a degree of acetalization of 22 mol%, a symmetry coefficient of 0.79, a Tg of 50°C, a Tm of 146°C, and a Tm / Tg(K / K) of 1.30.
[0197] 90 parts by mass of the acetalized ethylene vinyl alcohol copolymer (A-6) obtained and 10 parts by mass of the ethylene vinyl alcohol copolymer (EVOH2) obtained in Production Example 2 were mixed to obtain a composition which was melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet and laminated glass were obtained in the same manner as in Example 1.
[0198] <Comparative Examples 6-10> Except for changing the acetalized ethylene vinyl alcohol copolymer used as shown in Table 4, a molten kneaded product of the composition, a resin sheet, and laminated glass were obtained in the same manner as in Example 5.
[0199] The various physical properties of the compositions, resin sheets, and laminated glass obtained in Examples 5-13 and Comparative Examples 6-10 were evaluated according to the method described above. The results are shown in Tables 2-4.
[0200] [Table 2]
[0201] [Table 3]
[0202] [Table 4]
[0203] <Examples 14-17> Pelletized ethylene vinyl alcohol copolymer acetals (A-1') to (A-4') were obtained in the same manner as in Example 1, except that the reaction conditions were changed as shown in Table 4. The obtained ethylene vinyl alcohol copolymer acetals were porous bodies having a pore structure similar to that of the raw material ethylene vinyl alcohol copolymer. Using the obtained ethylene vinyl alcohol copolymer acetals, molten compound, resin sheet, and laminated glass were obtained in the same manner as in Example 1.
[0204] <Comparative Example 11> Except for changing the reaction conditions as shown in Table 4, EVOH acetal (B-2') was obtained in the same manner as in Comparative Example 1. Using the obtained EVOH acetal, a molten compound, a resin sheet, and laminated glass were obtained in the same manner as in Example 1.
[0205] <Comparative Example 12> Except for changing the reaction conditions as shown in Table 4, EVOH acetal (B-1') was obtained in the same manner as in Comparative Example 3. Using the obtained EVOH acetal, a molten compound, a resin sheet, and laminated glass were obtained in the same manner as in Example 1.
[0206] <Comparative Example 13> Except for changing the reaction conditions as shown in Table 4, the acetalized EVOH (B-4') was obtained in the same manner as in Comparative Example 4. Using the obtained acetalized EVOH, a molten compound, a resin sheet, and laminated glass were obtained in the same manner as in Example 1.
[0207] <Comparative Example 14> Except for changing the reaction conditions as shown in Table 4, the acetalized EVOH (B-5') was obtained in the same manner as in Comparative Example 5. Using the obtained acetalized EVOH, a molten compound, a resin sheet, and laminated glass were obtained in the same manner as in Example 1.
[0208] The various physical properties of the acetalized materials, resin sheets, and laminated glass obtained in Examples 14-17 and Comparative Examples 11-14 were evaluated according to the method described above. The results are shown in Table 5.
[0209] [Table 5]
[0210] <Examples 18-26> Except for changing the acetalized ethylene vinyl alcohol copolymer used as shown in Tables 6 and 7, molten kneaded compositions, resin sheets, and laminated glass were obtained in the same manner as in Examples 5 to 13.
[0211] <Comparative Examples 15-18> Except for changing the acetalized ethylene vinyl alcohol copolymer used as shown in Table 8, molten kneaded compositions, resin sheets, and laminated glass were obtained in the same manner as in Comparative Examples 6 and 8-10.
[0212] The various physical properties of the compositions, resin sheets, and laminated glass obtained in Examples 18-26 and Comparative Examples 15-18 were evaluated according to the method described above. The results are shown in Tables 6-8.
[0213] [Table 6]
[0214] [Table 7]
[0215] [Table 8]
[0216] <Example 27> (Synthesis of acetalized ethylene vinyl alcohol copolymers) 100 parts by mass of the EVOH porous material (EVOH1) obtained in Production Example 1 was dispersed in 377 parts by mass of water, and 19.5 parts by mass of isobutyraldehyde was added. The resulting dispersion was heated to 60°C under stirring. Stirring was continued for 2 hours to impregnate the ethylene vinyl alcohol copolymer with isobutyraldehyde. Then, at 60°C, 10 parts by mass of 1 M hydrochloric acid was added to the dispersion to carry out the acetalization reaction. Two hours after the first addition of hydrochloric acid, 40 parts by mass of 1 M hydrochloric acid was added, and the acetalization reaction was carried out for a further 6 hours. The acetal product produced by acetalization was in a solid state. Then, the acetalization reaction was stopped by neutralizing the dispersion with 75 parts by mass of 1 M sodium hydroxide. To neutralize the solid interior of the acetal product, the dispersion was stirred at 60°C for a further 8 hours. The neutralized acetalized material was filtered off, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it. The acetalized material was filtered off again, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it a second time. The washing water was filtered off, and vacuum drying was carried out at 60°C for 8 hours to obtain 103 parts by mass (100% yield) of pelletized ethylene vinyl alcohol copolymer acetalized material (A-7). The obtained EVOH acetalized material had an ethylene unit content of 44 mol%, a vinyl alcohol unit content of 36.4 mol%, and a degree of acetalization of 35 mol%. Furthermore, the obtained EVOH acetalized material was a porous body having a pore structure similar to that of the raw material EVOH1. The obtained acetal product of ethylene vinyl alcohol copolymer (A-7) had a symmetry coefficient of 0.82, a Tg of 44°C, a Tm of 140°C, a Tm / Tg (K / K) of 1.30, and an SP value of 11.5 (cal / cm²). 3 ) 1 / 2 The meso / racemo ratio was 2.2.
[0217] 100 parts by mass of the obtained ethylene vinyl alcohol copolymer acetal (A-7), and bis(2-butoxyethyl) adipate (manufactured by Tokyo Chemical Industry Co., Ltd.: DBEA, SP value 9.3 (cal / cm³) 3 ) 1 / 2 ) 11.5 parts by mass were melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was checked. No bleed-out was observed even after one week of standing. Laminated glass was also obtained using the resin sheet in the same manner as in Example 1.
[0218] <Example 28> 100 parts by mass of the acetalized product (A-2') of the ethylene vinyl alcohol copolymer obtained in Example 15, 4.0 parts by mass of bis(2-butoxyethyl) adipate (manufactured by Tokyo Chemical Industry Co., Ltd.: DBEA), and polypropylene glycol (average molecular weight 400: manufactured by Sanyo Chemical Industries, Ltd., "Sannix PP-400", SP value 10.4 (cal / cm³) 3 ) 1 / 2 ) 10.0 parts by mass was melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was checked. No bleed-out was observed even after one week of standing. Laminated glass was also obtained using the resin sheet in the same manner as in Example 1.
[0219] <Example 29> 100 parts by mass of the acetalized ethylene vinyl alcohol copolymer (A-7) obtained in Example 27, and monopropylene glycol dibenzoate (DIC Corporation: PB-10, SP value: 10.9 (cal / cm³)). 3 ) 1 / 2 A composition obtained by mixing 17.5 parts by mass of ) and 0.02 parts by mass of a phenolic antioxidant (BASF Japan Ltd., "Irganox 1010") was melt-kneaded for 3 minutes at a chamber temperature of 200°C and a rotation speed of 100 rpm using a laboplast mill. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was checked. No bleed-out was observed even after one week of standing. Laminated glass was also obtained using the resin sheet in the same manner as in Example 1.
[0220] <Example 30> 100 parts by mass of the acetal product (A-2') of the ethylene vinyl alcohol copolymer obtained in Example 15, and polypropylene glycol (average molecular weight 400: Sanyo Chemical Industries, Ltd., "Sannix PP-400", SP value 10.4 (cal / cm³) 3 ) 1 / 2 17.5 parts by mass were melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was checked. No bleed-out was observed even after one week of standing. Laminated glass was also obtained using the resin sheet in the same manner as in Example 1.
[0221] <Example 31> (Synthesis of acetalized ethylene vinyl alcohol copolymers) 100 parts by mass of the EVOH porous material (EVOH6) obtained in Production Example 6 was dispersed in 377 parts by mass of water, and 18.5 parts by mass of isobutyraldehyde was added. The resulting dispersion was heated to 60°C under stirring. Stirring was continued for 2 hours to impregnate the ethylene vinyl alcohol copolymer with isobutyraldehyde. Then, at 60°C, 10 parts by mass of 1 M hydrochloric acid was added to the dispersion to carry out the acetalization reaction. Two hours after the first addition of hydrochloric acid, 40 parts by mass of 1 M hydrochloric acid was added, and the acetalization reaction was carried out for a further 6 hours. The acetal product produced by acetalization was in a solid state. Then, the acetalization reaction was stopped by neutralizing the dispersion with 75 parts by mass of 1 M aqueous sodium hydroxide solution. To neutralize the solid interior of the acetal product, the dispersion was stirred at 60°C for a further 8 hours. The neutralized acetalized material was filtered off, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it. The acetalized material was filtered off again, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it a second time. The washing water was filtered off, and vacuum drying was carried out at 60°C for 8 hours to obtain 103 parts by mass (100% yield) of pelletized ethylene vinyl alcohol copolymer acetalized material (A-8). The obtained EVOH acetalized material had an ethylene unit content of 38 mol%, a vinyl alcohol unit content of 43.4 mol%, and a degree of acetalization of 30 mol%. Furthermore, the obtained EVOH acetalized material was a porous body having a pore structure similar to that of the raw material EVOH6. The symmetry coefficient of the obtained ethylene vinyl alcohol copolymer acetal (A-8) was 0.90, Tg was 50°C, Tm was 149°C, Tm / Tg(K / K) was 1.31, and the SP value was 12.0 (cal / cm²). 3 ) 1 / 2 The meso / racemo ratio was 2.1.
[0222] 100 parts by mass of the obtained ethylene vinyl alcohol copolymer acetal (A-8), and polypropylene glycol (average molecular weight 400: Sanyo Chemical Industries, Ltd., "Sannix PP-400", SP value 10.4 (cal / cm³) 3 ) 1 / 2 22.5 parts by mass were melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was checked. No bleed-out was observed even after one week of standing. Laminated glass was also obtained using the resin sheet in the same manner as in Example 1.
[0223] <Example 32> (Synthesis of acetalized ethylene vinyl alcohol copolymers) 100 parts by mass of the EVOH porous material (EVOH6) obtained in Production Example 6 was dispersed in 377 parts by mass of water, and 21.6 parts by mass of isobutyraldehyde was added. The resulting dispersion was heated to 60°C under stirring. Stirring was continued for 2 hours to impregnate the ethylene vinyl alcohol copolymer with isobutyraldehyde. Then, at 60°C, 10 parts by mass of 1 M hydrochloric acid was added to the dispersion to carry out the acetalization reaction. Two hours after the first addition of hydrochloric acid, 40 parts by mass of 1 M hydrochloric acid was added, and the acetalization reaction was carried out for a further 4 hours. The acetal product produced by acetalization was in a solid state. Then, the acetalization reaction was stopped by neutralizing the dispersion with 75 parts by mass of 1 M sodium hydroxide. To neutralize the solid interior of the acetal product, the dispersion was stirred at 60°C for a further 8 hours. The neutralized acetalized material was filtered off, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it. The acetalized material was filtered off again, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it a second time. The washing water was filtered off, and vacuum drying was carried out at 60°C for 8 hours to obtain 103 parts by mass (100% yield) of pelletized ethylene vinyl alcohol copolymer acetalized material (A-9). The obtained EVOH acetalized material had an ethylene unit content of 38 mol%, a vinyl alcohol unit content of 40.3 mol%, and a degree of acetalization of 35 mol%. Furthermore, the obtained EVOH acetalized material was a porous body having a pore structure similar to that of the raw material EVOH6. The obtained acetal product (A-9) of ethylene vinyl alcohol copolymer had a symmetry coefficient of 0.91, a Tg of 47°C, a Tm of 146°C, a Tm / Tg (K / K) of 1.31, and an SP value of 12.0 (cal / cm²). 3 ) 1 / 2 The meso / racemo ratio was 3.9.
[0224] 100 parts by mass of the obtained ethylene vinyl alcohol copolymer acetal (A-9), and polypropylene glycol (average molecular weight 400: Sanyo Chemical Industries, Ltd., "Sannix PP-400", SP value 10.4 (cal / cm³) 3 ) 1 / 2 17.5 parts by mass were melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was checked. No bleed-out was observed even after one week of standing. Laminated glass was also obtained using the resin sheet in the same manner as in Example 1.
[0225] <Example 33> 100 parts by mass of the acetalized product (A-2') of the ethylene vinyl alcohol copolymer obtained in Example 15 and triethylene glycol di-2-ethylhexoate ("3G8", SP value: 9.1 (cal / cm³) 3 ) 1 / 2 ) 7.5 parts by mass were melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was observed after 3 days of standing. Laminated glass was obtained using the resin sheet in the same manner as in Example 1.
[0226] <Example 34> 100 parts by mass of the acetal product (A-2') of the ethylene vinyl alcohol copolymer obtained in Example 15 and glycerin mono-12-hydroxystearate (GMS-12) (HC-12, manufactured by Riken Vitamin Co., Ltd., SP value: 12.1 (cal / cm³) 3 ) 1 / 2 ) 10.0 parts by mass was melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was observed after 3 days of standing. Laminated glass was obtained using the resin sheet in the same manner as in Example 1.
[0227] <Comparative Example 19> 100 parts by mass of the acetalized ethylene vinyl alcohol copolymer (B-1') obtained in Comparative Example 12 and 4.0 parts by mass of bis(2-butoxyethyl) adipate (manufactured by Tokyo Chemical Industry Co., Ltd.: DBEA) were melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was observed after 3 days of standing. Laminated glass was obtained using the resin sheet in the same manner as in Example 1.
[0228] <Comparative Example 20> 100 parts by mass of the acetalized ethylene vinyl alcohol copolymer (B-1') obtained in Comparative Example 12, 11.5 parts by mass of polypropylene glycol (average molecular weight 400: Sanyo Chemical Industries, Ltd., "Sannix PP-400" (SP value 10.4)), and 0.02 parts by mass of a phenolic antioxidant (BASF Japan Ltd., "Irganox 1010") were melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was checked. No bleed-out was observed even after 7 days of standing. Laminated glass was obtained using the resin sheet in the same manner as in Example 1.
[0229] <Comparative Example 21> 100 parts by mass of the acetalized product (B-4') of the ethylene vinyl alcohol copolymer obtained in Comparative Example 13, and polypropylene glycol (average molecular weight 400: Sanyo Chemical Industries, Ltd., "Sannix PP-400", SP value 10.4 (cal / cm³) 3 ) 1 / 2 ) 10.0 parts by mass was melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. Since plasticizer bleed-out was observed immediately after the resin sheet was prepared, analysis of the resin sheet and the preparation of laminated glass were not carried out.
[0230] <Comparative Example 22> (Synthesis of acetalized ethylene vinyl alcohol copolymers) 100 parts by mass of the EVOH porous material (EVOH6) obtained in Production Example 6 was dispersed in 377 parts by mass of water, and 1.6 parts by mass of isobutyraldehyde was added. The resulting dispersion was heated to 60°C under stirring. Stirring was continued for 2 hours to impregnate the ethylene vinyl alcohol copolymer with isobutyraldehyde. Then, at 60°C, 10 parts by mass of 1 M hydrochloric acid was added to the dispersion to carry out the acetalization reaction. Two hours after the first addition of hydrochloric acid, 40 parts by mass of 1 M hydrochloric acid was added, and the acetalization reaction was carried out for a further 6 hours. The acetal product produced by acetalization was in a solid state. Then, the acetalization reaction was stopped by neutralizing the dispersion with 75 parts by mass of 1 M sodium hydroxide. To neutralize the solid interior of the acetal product, the dispersion was stirred at 60°C for a further 8 hours. The neutralized acetalized material was filtered off, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it. The acetalized material was filtered off again, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it a second time. The washing water was filtered off, and vacuum drying was carried out at 60°C for 8 hours to obtain 103 parts by mass (100% yield) of pelletized ethylene vinyl alcohol copolymer acetalized material (B-6). The obtained EVOH acetalized material had an ethylene unit content of 38 mol%, a vinyl alcohol unit content of 60.3 mol%, and a degree of acetalization of 2.6 mol%. Furthermore, the obtained EVOH acetalized material was a porous material having a pore structure similar to that of the raw material EVOH6. The obtained acetal product (B-6) of ethylene vinyl alcohol copolymer had a symmetry coefficient of 0.78, a Tg of 54°C, a Tm of 167°C, a Tm / Tg(K / K) of 1.35, an SP value of 13.1, and the meso / racemo ratio could not be calculated due to low peak intensity.
[0231] 100 parts by mass of the obtained ethylene vinyl alcohol copolymer acetal (B-6) and polypropylene glycol (average molecular weight 400: Sanyo Chemical Industries, Ltd., "Sannix PP-400", SP value 10.4 (cal / cm³) 3 ) 1 / 2 ) 10.0 parts by mass was melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. Since plasticizer bleed-out was observed immediately after the resin sheet was prepared, analysis of the resin sheet and the preparation of laminated glass were not carried out.
[0232] <Comparative Example 23> (Synthesis of acetalized ethylene vinyl alcohol copolymers) 100 parts by mass of the EVOH porous material (EVOH1) obtained in Production Example 1 was dispersed in 377 parts by mass of water, and 33.0 parts by mass of isobutyraldehyde was added. The resulting dispersion was heated to 60°C under stirring. Stirring was continued for 2 hours to impregnate the ethylene vinyl alcohol copolymer with isobutyraldehyde. Then, at 60°C, 10 parts by mass of 1 M hydrochloric acid was added to the dispersion to carry out the acetalization reaction. Two hours after the first addition of hydrochloric acid, 40 parts by mass of 1 M hydrochloric acid was added, and the acetalization reaction was carried out for a further 6 hours. The acetal product produced by acetalization was in a solid state. Then, the acetalization reaction was stopped by neutralizing the dispersion with 75 parts by mass of 1 M sodium hydroxide. To neutralize the solid interior of the acetal product, the dispersion was stirred at 60°C for a further 8 hours. The neutralized acetalized material was filtered off, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it. The acetalized material was filtered off again, and 500 parts by mass of deionized water was added to the acetalized material and stirred at 60°C for 6 hours to wash it a second time. The washing water was filtered off, and vacuum drying was carried out at 60°C for 8 hours to obtain 103 parts by mass (100% yield) of pelletized ethylene vinyl alcohol copolymer acetalized material (B-7). The obtained EVOH acetalized material had an ethylene unit content of 44 mol%, a vinyl alcohol unit content of 24.4 mol%, and a degree of acetalization of 56 mol%. Furthermore, the obtained EVOH acetalized material was a porous material having a pore structure similar to that of the raw material EVOH1. The obtained acetal product (B-7) of ethylene vinyl alcohol copolymer had a symmetry coefficient of 0.89, a Tg of 42°C, a Tm of 125°C, a Tm / Tg(K / K) of 1.26, an SP value of 10.7, and a meso / racemo ratio of 6.7.
[0233] 100 parts by mass of the obtained ethylene vinyl alcohol copolymer acetal (B-7) and polypropylene glycol (average molecular weight 400: Sanyo Chemical Industries, Ltd., "Sannix PP-400", SP value 10.4 (cal / cm³) 3 ) 1 / 2 ) 10.0 parts by mass was melt-kneaded using a laboplast mill at a chamber temperature of 200°C and a rotation speed of 100 rpm for 3 minutes. The contents of the chamber were removed and cooled to obtain a molten mixture. Using the obtained molten mixture, a resin sheet was obtained in the same manner as in Example 1. The resin sheet was left to stand in a constant temperature and humidity chamber at 23°C and 50% RH for one week, and plasticizer bleed-out was checked. No bleed-out was observed even after 7 days of standing. Laminated glass was obtained using the resin sheet in the same manner as in Example 1.
[0234] The various physical properties of the compositions, resin sheets, and laminated glass obtained in Examples 27-34 and Comparative Examples 19-23 were evaluated according to the method described above. The results are shown in Tables 9-10.
[0235] [Table 9]
[0236] [Table 10]
[0237] As shown in Tables 1-10, the resin sheets obtained in the examples were found to have superior transparency, puncture resistance, and self-supporting and creep resistance in high-temperature environments compared to the comparative examples. In particular, Examples 1-10 and 14-23 had a slow-cooling haze of 2% or less, very high transparency, and good film-forming properties. Therefore, the acetalized ethylene vinyl alcohol copolymer and composition of the present invention can form resin sheets that have excellent transparency and puncture resistance, as well as excellent self-supporting and creep resistance in high-temperature environments.
[0238] Furthermore, as shown in Table 9, the resin sheets obtained in Examples 27-32, which used a specific amount of plasticizer having a specific SP value, exhibited excellent bleed-out resistance and good results in the ball-dropping test, confirming that the laminated glass had superior penetration resistance.< / tms>
Claims
1. An acetalized product of an ethylene-vinyl alcohol copolymer, Based on the total monomer units constituting the acetalized product, 20 to 80 mole % ethylene units, and 4 to 76 mol % vinyl alcohol units Including, The degree of acetalization is 5 to 80 mol %, Formula (1): 0.75≦W 0.05h / 2f≦1.00 (1) [In formula (1), W 0.05h / 2f represents a symmetry coefficient determined by reversed-phase partition gradient high-performance liquid chromatography analysis using a water-ethanol eluent in accordance with JIS K 0124:2011. and formula (2): 1.27≦Tm / Tg≦1.35 (2) [In formula (2), Tm and Tg represent the melting peak temperature (Kelvin) and the midpoint glass transition temperature (Kelvin), respectively, measured in accordance with JIS K7121:2012.] Fulfilling The acetalized product of the ethylene-vinyl alcohol copolymer, wherein the ethylene-vinyl alcohol copolymer has a specific surface area of 25 m 2 / g or more.
2. An acetalized product of an ethylene-vinyl alcohol copolymer, Based on the total monomer units constituting the acetalized product, 20 to 80 mole % ethylene units, and 4 to 76 mol % vinyl alcohol units Including, The degree of acetalization is 5 to 80 mol %, Formula (1): 0.75≦W 0.05h / 2f≦1.00 (1) [In formula (1), W 0.05h / 2f represents a symmetry coefficient determined by reversed-phase partition gradient high-performance liquid chromatography analysis using a water-ethanol eluent in accordance with JIS K 0124:2011. Fulfilling The meso / racemo ratio of the acetal ring structure is less than 5; The acetalized product of the ethylene-vinyl alcohol copolymer, wherein the ethylene-vinyl alcohol copolymer has a specific surface area of 25 m 2 / g or more.
3. The acetalized product according to claim 1, wherein the meso / racemo ratio of the acetal ring structure is less than 5.
4. SP value is 12.6 (cal / cm 3 ) 1/2 The acetalized product according to any one of claims 1 to 3, which is as follows:
5. The acetalized product according to any one of claims 1 to 4, having a degree of acetalization of 5 to 62 mol%.
6. An acetal compound (A) according to any one of claims 1 to 5, and at least one component selected from the group consisting of a resin (B) other than the acetalized product (A), a plasticizer, an antioxidant, and an ultraviolet absorber; and the content of the acetalized product (A) is 70 mass% or more.
7. The composition according to claim 6, wherein the melting peak temperature Tms measured in accordance with JIS K7121:2012 is 120 ° C. to 180 ° C.
8. The composition according to claim 6 or 7, wherein the content of the plasticizer is 40 parts by mass or less based on 100 parts by mass of the acetalized product (A).
9. The composition according to any one of claims 6 to 8, wherein the content of the plasticizer is 10 to 40 parts by mass per 100 parts by mass of the acetalized product (A).
10. The SP value of the plasticizer is 9.2 to 12.0 (cal / cm 3 ) 1/2 The composition according to any one of claims 6 to 9,
11. The resin (B) is an ethylene-vinyl alcohol copolymer and / or a copolymer represented by the following formula (3): Tm / Tg<1.27 (3) [In formula (3), Tm and Tg represent the melting peak temperature (Kelvin) and the midpoint glass transition temperature (Kelvin), respectively, measured in accordance with JIS K7121:2012.] The composition according to any one of claims 6 to 10, wherein the acetalized product (B) of an ethylene-vinyl alcohol copolymer satisfies the above.
12. The following formula (4): ΔH AH / ΔH A ≦0.30 (4) [In formula (4), ΔH A indicates the heat of crystal fusion measured using a differential scanning calorimeter (DSC) when the temperature is increased from 25° C. to 140° C. at a rate of 10° C. / min, held at 140° C. for 30 minutes, then decreased from 140° C. to −30° C. at a rate of 4° C. / min, and then increased again from −30° C. to 200° C. at a rate of 10° C. / min. AH is the ΔH A The heat of crystal fusion on the high-temperature side when the peak is split at 145°C is shown. The composition according to any one of claims 6 to 11,
13. (i) preparing a dispersion containing an ethylene-vinyl alcohol copolymer, an aldehyde, and a solvent, and impregnating at least a portion of the aldehyde into the ethylene-vinyl alcohol copolymer; and (ii) After step (i), a step of adding a catalyst to the dispersion to acetalize the ethylene-vinyl alcohol copolymer. Including, The ethylene-vinyl alcohol copolymer is a porous body, The method for producing an acetalized product according to any one of claims 1 to 5, wherein the acetalization is carried out by a solid-liquid reaction.
14. A resin sheet comprising at least one layer containing the acetalized product according to any one of claims 1 to 5 or the composition according to any one of claims 6 to 12.
15. An interlayer film for laminated glass, comprising the resin sheet according to claim 14.
16. A laminated glass comprising two glass sheets and the interlayer film for laminated glass according to claim 15 disposed between the two glass sheets.